Genome sequencing and transcriptome analysis of Corbicula fluminea reveal its genome evolution and the role of glutathione S-transferase and glutathione peroxidase families in salinity response - Ting Zhang; Yidong Liang; Junlei Ma; Jinshuo Liang; Yicheng Li; Yanfeng Zhou; Dongpo Xu (Aquaculture, 2027)

Integration of physiological, transcriptomic and metabolomic analyses reveals acute carbonate alkalinity stress responses in the gill of Asian clam (Corbicula fluminea) - Ting Zhang; Junlei Ma; Yidong Liang; Yicheng Li; Jinshuo Liang; Yanfeng Zhou; Dongpo Xu (Aquaculture, 2027)

Thiocyanate-driven denitrification with mixotrophic flexibility for real coking wastewater treatment: Novel insights into nitrogen cycling - Yu Zhang; Yu-Tong Li; Quan Zhang; Xue-Ting Wang; Wei Wang; Aijie Wang; Jun Ma; Duu-Jong Lee; Nanqi Ren; Chuan Chen (Water Research, 2026)

Hepatotoxicity of OBS: A review of the emerging PFOS substitute - Haibo Jin; Mingyue Wang; Ting Tian; Tan Ma; Lili Yang; Hongliang Li; Jingyan Liang (Toxicology Letters, 2026)

Preparation and performance analysis of a novel composite dust suppressant considering wind and train vibration effects - Hao-kui Wang; Ming-yi Chen; Zi-ting Pei; Fu-chao Tian; Yue Ren; Xing-jun Ma; Ming-xin Li (Journal of Environmental Chemical Engineering, 2026)

A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

Theaflavins delays the odor deterioration of unwashed surimi products during gel processing and frozen storage - Chaofei Sun; Ting Wen; Xianghong Li; Jian Yu; Yiqun Huang; Xiayin Ma; Shuang Li; Yongle Liu; Dongmin Liu; Faxiang Wang (Food Control, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

A synthetic microbial community for the enhanced removal of complex emerging pollutants from domestic wastewater - Ting Xu; Hui Yun; Yuru Zhao; Yue He; Siyu Chen; Ting Ma; Wenjie Zhang; Liang Peng; Xiangkai Li (Journal of Hazardous Materials, 2026)

Regenerable “Two-in-One” molecularly imprinted nanozymes colorimetric sensor array combined with deep learning enables selective removing and visual discriminate of tetracycline antibiotics - Yudan Wang; Yupeng Li; Gaoyuan Zuo; Ting Li; Yating Chen; Ting Wu; Xinrui Chen; Yiyang Ma; Meihong Li; Weimin Yang; Guiping Qin; Xinrong Guo; et al. (Journal of Hazardous Materials, 2026)

Freeze-dried chocolate as a one-bite carrier for calcium, magnesium and vitamin D3: uniform codelivery with enhanced stability, instant disintegration and site-specific release - Qianqian Li; Lu Yang; Ting Xu; Yuhui Wang; Lulu Zhang; Juan Hao; Yuwei He; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2026)

Integrating water use efficiency dynamics into ecological function zoning: Patterns, drivers, and trade-offs - Libin Zhang; Jiaxing Zhang; Qiang Ma; Jianzhu Li; Keke Zhou; Ting Zhang; Ping Feng (Environmental Research, 2026)

A novel fever prevalence indicator for early warning of acute respiratory infections using wastewater-based epidemiology and machine learning - Xue-Ting Shao; Hao-Yang Li; Jing-Bo Guan; Xin-Dong Ma; De-Gao Wang (Environmental Research, 2026)

Ozone exposure and the risk of gestational hypertension in a northern Chinese city: Identifying the critical windows of exposure - Zhihua Gong; Pannan Li; Li Ma; Zhihong Li; Qinqin Tian; Ting Du; Yike Li; Yabin Hou; Yongnian Zhou; Guangke Li; Nan Sang (Environmental Pollution, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Redox-sensitive genetic circuits enhance microbial stress tolerance to complex inhibitors in lignocellulose biorefinery - Wen-Tao Wang; Qi Feng; Ting-Ting Li; Muhammad Aamer Mehmood; Hui Zhu; Ning Wang; Yi Ma; Chen-Guang Liu; Feng-Wu Bai (Chemical Engineering Journal, 2026)

Nanostructured Fe2(MoO4)3 cathodes: Enhancing ion and electron kinetics for high-rate and low-temperature sodium-ion batteries - Ting Zhao; Hang Liu; Gacao Dou; Dongting Zhang; Junqiang Qiao; Juan Yang; Pengjun Ma; Cuiying Lu; Hongxia Li; Hongruo Ma; Kunjie Wang; Bingjun Yang (Chemical Engineering Journal, 2026)

The role of taste receptor T1R1/T1R3 in autophagy regulation of spermatogenic cells and its association with spermatogenesis in Xiang pigs - Mengting Huang; Aixia Li; Rongjiang Ma; Yi Gao; Yuxuan Jia; Xiangyu Shen; Minghong Xie; Liang Yang; Kangsen Shen; Zheng Ao; Yiyu Zhang; Xiang Chen; et al. (Animal Reproduction Science, 2026)

Comprehensive Transcriptomics and Biochemical Analysis Provide New Insights into the Light Intensity Regulation Growth and Medicinal Quality of Dendrobium nobile - Ting Li; Haolin Liu; Yijun Fan; Hui Wang; Linlong Xu; Siyu He; Jie Ma; Junlan Wu; Chunhong Mou; Meng Zhao; Li Chen; Xuyang Liu; et al. (Journal of Plant Growth Regulation, 2026)

Erratum to “Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives” [Water Research, Volume 300, 1 August 2026, 125856] - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Sulfur disproportionation in engineered environmental systems: A critical review of mechanisms, applications, and emerging perspectives - Yu Zhang; Yu-Tong Li; Quan Zhang; Wei Wang; Xue-Ting Wang; Lei Zhao; Ai-jie Wang; Jun Ma; Duu-Jong Lee; Nan-qi Ren; Chuan Chen (Water Research, 2026)

Synergistic design of oxygen-rich and microporous biomass derived carbon for the catalytic adsorption of cyanide gases - Yali Wang; Mingzhe Ma; Shicai Liu; Xueyuan Pan; Yanren Jin; Ting Zhao; Ao Wang; MengMeng Fan; Da Li; Kang Sun; Jianchun Jiang; Hao Sun (Journal of Environmental Chemical Engineering, 2026)

A Synergistic Botanical Compound Preparation of Ganoderma lucidum, Lycium ruthenicum, and Red Ginseng Alleviates Exercise-Induced Fatigue via Coordinated Regulation of Energy Metabolism, Oxidative Stress, and Gut Microbiota in Mice - Tao Liu; Mengmin Li; Wanyun Xu; Zhenhao Li; Yuanxiang Jin; Ting Luo; Tao Ma; Jintao Cheng; Shiyu Li; Qingchi Wang; Kan Shao; Yi Yang; et al. (Food Bioscience, 2026)

Spinel LiMn2O4 stabilized by Fe/Sb co-doping mediated MnO bond modulation for high-efficiency lithium extraction from brine - Wenjie Fan; Luxiang Ma; Huifang Li; Wencheng Pan; Xin Zeng; Ting Li; Zhixiang Li (Desalination, 2026)

Fulvic acid loading controls the retention-mineral stabilization trade-off of arsenate during oxic ferrihydrite aging - Wei Yu; Fan Mo; Jingyuan Dai; Chenxi Zhang; Kaixuan Wang; Ting Ma; Haishen Jiang; Xi Chen; Xiaoming Zhao; Haibo Li (Chemical Engineering Journal, 2026)

HSF1 inhibits smooth muscle gene program to enhance white fat browning and hypermetabolism after burn injury - Yankang Zhang; Yuhan Zheng; Bin Chen; Xinqian Li; Ting Zhang; Lingyan Xu; Jing Ma; Xinran Ma; Yu Li (Science China Life Sciences, 2026)

Effect of explicit intermediate layer on the solution accuracy of the thermal stress for printed circuit heat exchangers with the homogenization method - Xiaoxu Zhang; Zirui Xu; Enhui Li; Yin Tan; Jiyuan Bi; Dan Zheng; Sheng Wang; Ting Ma (Annals of Nuclear Energy, 2026)

Four new cytotoxic triterpenoids from Euphorbia fischeriana - Yuan-Biao He; Yan-Ni Ma; Yu-Ping Huang; Wen-Na Li; Ting-Xiang Shi; Jing Yang; Yong Zhao (Natural Product Research, 2026)

Rapid identification of binary and ternary adulteration in camellia oil by CRISPR/Cas12a assay - Ting Shi; Tenghui Dai; Jing Zhou; Juan Li; Lulu Zhang; Jieyu Cui; Xiaodong Ma; Junbiao Dai; Ailiang Chen; Xinjie Wang (Food Chemistry, 2026)

The mechanism of LuxS/AI-2 QS system regulating the biofilm formation of Lactobacillus plantarum SDJ09 - Mengyu Liu; Xiaochun Su; Ting Ma; Lijia Liu; Jiamin Xu; Xiaoling Liu; Yunxia Bai; Shubo Li; Yuan Guo (Probiotics and Antimicrobial Proteins, 2026)

Multitrophic predators shape and stabilize soil microbiome networks at a regional scale - Nan Jiang; Chunhui Liu; Huiping Ma; Yue Hu; Shi Cheng; Qijun Wu; Gen Li; Huixin Li; Ting Liu (Applied Soil Ecology, 2026)

Dysregulated KIF2A correlates with p53 expression pattern in breast cancer - Yun Hao; Si-Qin Ma; Ting Xu; Jia-Qi Wu; Rong Ma; Ya-Wen Wang; Jian-Li Wang (Molecular and Cellular Biochemistry, 2026)

High-density lipoprotein antioxidant function is associated with lipid profiles and lipid-lowering therapy - Hong-Yu Cao; Zhi-Wei Mo; Zhen-Sheng Ma; Yi-Fang Liu; Chen Wang; Yue-Ming Peng; Yue-Ting Kang; Yan Li; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2026)

Research on the Highly Efficient and Low-Dose Improvement of Alcohol-Induced Liver Injury by High-Selenium-Content Modified Lycium barbarum Polysaccharides - Shuangzhe Mao; Xin Zhang; Lulu Wei; Han Zhang; Abo Li; Mengmeng Sun; Jiao Feng; Ting Ren; Yiting Huang; Xiaoying Liu; Zhifeng Zhang; Zhihui Zhao; et al. (Biological Trace Element Research, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Four new cysteine derivatives with cytotoxic activity from Poecilobdella manillensis - Qingqing Fan; Peixing He; Hang Xiao; Juan He; Ting Wang; Zhenbei Lan; Feng Tian; Jianyuan Tang; Li Ma (Phytochemistry Letters, 2026)

From lepidolite acid leachate to phosphate adsorbent: selective Al/Fe recovery and conversion to Al-Fe composite hydroxide - Shuangli Xi; Jingrui Li; Youcai Ma; Jing Guo; Wentao Li; Ting Yang; Guocan Zheng; Changyuan Tao; Zuohua Liu (Journal of Environmental Chemical Engineering, 2026)

Phosphorus-modified biochar for heavy metal passivation and soil improvement: from preparation to mechanistic understanding - Ting Ma; Yingying Wu; Haibo Li (Journal of Environmental Chemical Engineering, 2026)

Risk assessment, source apportionment and driving mechanism of soil heavy metals in coal mining areas of Xinjiang, China - Xin He; Fei Zhang; Ting Zhou; Boyu Wang; Xuan Zhang; Xiangyu Liu; Zia Ahmed; Mou Leong Tan; Ziheng Feng; Zhihui Li; Xu Ma (Gondwana Research, 2026)

The conversion of ether into ester functional groups of porous carbon through altering intramolecular condensation pathways - Ting Xiao; Yin Yang; Yulong Li; Chen Zhang; Changbo Lu; Qiankun Xiang; Henglong Ren; Shengping Li; Haipeng Song; Yindong Liu; Luhai Wang; Xinlong Ma (Chemical Engineering Journal, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Interface-engineered MXene/OCNT fibers for high-performance wearable supercapacitors - Rui Wang; Xupu Jiang; Ting Ding; Wujun Ma; Chuntao Lan; Min Li (Chemical Engineering Journal, 2026)

Directed synthesis, characterization and rheological properties of an ultrahigh molecular weight acetylated-gellan gum - Yue Ming; Zhuangzhuang Shi; Weilong Wang; Jue Li; Yiting Lin; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Antimicrobial resistance analysis of Escherichia coli isolated from foxes in China - Hao Ni; Jiagong Hou; Qing-Yu Hou; Chao Xu; Xue Leng; Xue-Min Li; Ya Qin; Shuo Liu; Meng-Ting Yang; Lu-Yao Tang; Yu-Zhe Sun; Quan Zhao; et al. (Veterinary Research Communications, 2026)

Improved eradication of apple stem grooving virus and apple chlorotic leaf spot virus in apple rootstocks by combining thermotherapy with electrotherapy - Xiao-Yan Ma; Qing Li; Zhi-Wei Kang; Ming-Yuan Jing; Ya-Ting Zhang; Min-Rui Wang; Dong Zhang; Lu Bao; Juan-Juan Ma (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Experimental study on microwave-assisted mechanical fragmentation of simulated vesicular mare basalt - Liang-Xiao Chen; Zheng-Wei Li; Xia-Ting Feng; De-Tian Li; Cheng-Dan He; Xian-Qiang Li; Yong-Jun Wang; Wen-Feng Guo; Jian Ma (International Journal of Rock Mechanics and Mining Sciences, 2026)

Association between maternal physical activity and casein content in breast milk from the YI cohort: A preterm and term infant comparison - Jianlan Xue; Ting Li; Yan Feng; Xinyue Wang; Sufang Duan; Xiaoqin Luo; Jianhua Ma; Li Su (International Dairy Journal, 2026)

Ultrasound-induced modifications of fish proteins: a comprehensive review of structural, physicochemical, functional properties, and industrial applications - Qingzhi Ding; R.A. Dilmi Anuththara Ranasinghe; Zijie Mo; Huamin Yang; Lin Luo; Haile Ma; Xiaoran Li; Chunhua Dai; Ting Zhang (Food Research International, 2026)

Quercetin ameliorates intestinal barrier dysfunction by suppressing the PKCα/MLCK signaling pathway in piglets - Qiuyu Chen; Huadi Mei; Mengyao Fang; Yiyan Cui; Ting Rong; Dun Deng; Zhimei Tian; Min Song; Zhenming Li; Zhichang Liu; Xianyong Ma; Miao Yu (Food Research International, 2026)

Analysis of quality deterioration of buckwheat hele noodles during freezing storage: oxidation of lipids and proteins - Ting Yu; Yalei Li; Ruiming Luo; Shuang Gao; Qijian Jiang; Mengyao Ma; Lingling Zhang; Yuying Xiao (Food Chemistry, 2026)

Quantitative reconstruction of the paleoclimate over the past 200 years in the northern margin of the east Asian summer monsoon, China - Yan-Xia Xue; Hong-Wei Meng; Yu-Zhen Ma; Chao Guo; Ting-Yong Li; Cai-Ming Shen (CATENA, 2026)

RCTUnet: a deep learning model for crop-residue-soil image segmentation and crop residue cover extraction - Ting Li; Yang Liu; Haikuan Feng; Meiyan Shu; Hao Yang; Yuanyuan Fu; Xin Xu; Yinghao Lin; Hongbo Qiao; Wei Guo; Xinming Ma; Lei Shi; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Extracellular vesicle-derived CDCP1 promotes chemoresistance and macrophage polarization in breast cancer - Yibing Liu; Li Ma; Ting Zhu; Di Wu; Yonglei Liu (Human Cell, 2026)

Two new sesquiterpenes from Ainsliaea glabra - Xiao-Li Ma; Guo-Dong Jiang; Ji-Yuan Wei; Ze-Dong Nan; Chang-Ting Zhang; Zhi-Jun Song (Natural Product Research, 2026)

Crystallize and protonate: A dual-boosting strategy for photocatalytic NO abatement over carbon nitride - Haonan Hu; Bin Liu; Xianli Hu; Hao Ma; Ting Zhang; Jinwu Bai; Wei Xu; Ruimei Fang; Yuhan Li; Fan Dong (Journal of Environmental Sciences, 2026)

Basic amino acid-enriched egg white peptides for efficient repair of intestinal injury: Preparation, application, and mechanism analysis - Qingwen Han; Jingbo Liu; Shengrao Li; Mohan Zhang; Weiyi Ma; Yanguo Huan; Dongfang Wang; Yongqi Yu; Ting Zhang; Siwen Lyu (Food Research International, 2026)

Exploring the formation pathways of characteristic volatile organic compounds after walnut roasting based on HS-SPME-GC-MS and multivariate statistical analysis - Kaiyang Zhu; Ji Ma; Ruona Li; Hafiz Muhammad Mubeen; Ting Zhang; Hongjie Lei; Wenge Zhao; Huaide Xu; Mei Li (Food Chemistry, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Engineering compartmentalized utilization of glycerol with glucose for high-level chondroitin production in Corynebacterium glutamicum - Zhuangzhuang Shi; Yue Ming; Jue Li; Yiting Lin; Weilong Wang; Wei Sha; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2026)

Valorization of oily sludge with coal gasification slag via catalytic pyrolysis - Lei Han; Hai-Jie Hu; Jia-Xuan Liu; Tao Yu; Jin-Ling Li; Lan-Ting Ma; Cheng-Tun Qu; Zhong-Wen Liu (Bioresource Technology, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

The evolutionary path of widespread IR heteroplasmy of chloroplast genomes in the context of Rhodophyta phylogeny - Yang Li; Xiaomei Huang; Yuanhao Li; Ting Wang; Yuhui Xing; Jingjing Guo; Xiaoya Ma; Bojian Zhong (Journal of Molecular Evolution, 2026)

Particulate matter generated from electrolysis processes: a review of pollution, formation, and control technologies - Zizhen Ma; Lingyu Li; Qingyuan Hao; Linhua Jiang; Ning Duan; Fuyuan Xu; Lei Duan; Jingkun Jiang; Yanhui Wang; Yan Tan; Huawei Zhang; Ting Liu; et al. (ENGINEERING Environment, 2026)

Morphology-dependent biotoxic effects and cellular damage mechanisms of silver nanoparticles on Chlorella vulgaris and Scenedesmus obliquus - Wei Yu; Yongchang Shang; Zhenyu Wang; Yue Yang; Chenxi Zhang; Ningcan Deng; Kaixuan Wang; Ting Ma; Xiuzhen Yang; Miao Xu; Fan Mo; Haibo Li (Algal Research, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Association between heavy-duty vehicle pollution exposure and cardiovascular disease: A cohort study of middle-aged and elderly adults - Xin Ma; Juan Hao; Jinghua Wang; Yan Li; Xianjia Ning; Hongjun Mao; Ting Wang (Journal of Environmental Sciences, 2026)

Effects of polystyrene nanoplastics on tomato plant growth, fruit yield and quality - Mingyuan You; Ting Zhou; Jiahui Yan; Jingyue Ma; Tingting Kong; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Food Chemistry, 2026)

Impact of konjac glucomannan on starch digestibility: An in - depth exploration of properties and dynamics - Ting Li; Yingjuan Zhang; Peng Guo; Chenjie Wang; Dongliang Zhang; Chengye Ma (Food Hydrocolloids, 2026)

Interfacial properties and emulsification performance of methyl-esterified okra polysaccharides - Ting Xu; Bingjie Zhang; Guojun Liu; Hongxu Gao; Panshu Ma; Yepeng Pang; Yuchao Gu; Mingyan Yan; Yinping Li (Food Hydrocolloids, 2026)

Bacterial cellulose/tea polyphenol films from tea waste via anaerobic synthesis: A sustainable material for active food preservation - Ge Gao; Haolong Zheng; Shaofang Niu; Yi Wang; Xueqing Zhao; Yucheng Shi; Liyuan Sun; Mingchang Li; Guoqiang Li; Ting Ma (Food Packaging and Shelf Life, 2026)

Alisol B 23-acetate alleviates high-fat diet-induced insulin resistance by activating the SIRT1/FOXO1 axis and PI3K/AKT pathway - Wenjun He; Zhenxuan Kong; Jingshu Cai; Zhuyun Wang; Li Ma; Xiaoqiu Xiao; Ting Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Physiological and Secondary Metabolism of Dendrobium nobile Lindl in Response to High Temperature Stress - Linlong Xu; Yijun Fan; Xueyan Tan; Jie Ma; Ting Li; Siyu He; Hui Wang; Liangjie Zhu; Le Zeng; Aoxue Luo (Journal of Plant Growth Regulation, 2026)

Research progress on chemical constituents and biological activities of medicinal plants from Euonymus genus - Ying-Jun Ma; Xin-Ru Li; Meng-Qi Gao; Jia-Jia Liu; Ammara Khalid; Jie-Ting Chen; Fan-Cheng Meng (Natural Product Research, 2026)

miR-17195 promotes infectious bronchitis virus proliferation and macrophage-mediated inflammation via the PLCβ2-TAK1 axis - Zheng Wang; Chi Liu; Xuan Chen; Jianlan Li; Waner Li; Zhaxi Duoji; Qingcheng Yang; Ting Xu; Anyun Zhang; Peng Ma; Hongning Wang (Veterinary Microbiology, 2026)

Onset timing and palaeoenvironmental records of Carnian Pluvial Episode (Late Triassic) in southwestern Guizhou, China - Shi-Xin Li; Zhi-Heng Ma; Xi Zhang; Wei Yang; Jian-Li Zeng; Mihai Emilian Popa; Kai-Nan Mao; Ting-Shan Zhang (Palaeoworld, 2026)

Application of machine learning in radiolarian taxonomy: A case study on Early Cretaceous Turbocapsula lineage - Xin-Yi Zhang; Han-Ting Zhong; Xin Li; Hui Chen; Shan Ye; Ming-Cai Hou; Chao Ma (Palaeoworld, 2026)

Corrigendum to “Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression” [Chem. Eng. J. 527 (2026) 171844/ CEJ_171844] - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Transforming Camellia oleifera meal into feedstuff: Enhancing value through detoxification and fermentation - Yiyan Cui; Yuheng Lei; Zhenming Li; Zhichang Liu; Min Song; Dun Deng; Zhimei Tian; Ting Rong; Pan Yang; Xianyong Ma; Miao Yu (Bioresource Technology, 2026)

Taurine Alleviates Sepsis-Induced Myocardial Injury by Inhibiting NF-κB Pathway-Mediated Inflammation, Mitochondrial Dysfunction, and Apoptosis - Junkai Feng; Ting Ma; Liu Yang; Min Li; Dahai Xiao; Pengxin Gong; Ani Zhao; Pu Li; Linong Yao (Cardiovascular Toxicology, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Boosting heterogeneous advanced oxidation processes: Curvature-driven nanotube confinement catalysis - Ting Ma; Fan Mo; Haibo Li; Yu Shang; Kaixuan Wang; Xiangqi Nie (Water Research, 2026)

Soil aggregate carbon stocks and sequestration efficiency under long-term fertilization across China’s croplands - Man Cheng; Zhixuan Chen; Ting Shi; Haiyang Ma; Yongli Wen; Puwang Li; Minggang Xu (Soil and Tillage Research, 2026)

Toxicity evaluation of fosthiazate to Bombyx mori Linnaeus (Lepidoptera: Bombycidae): A new perspective from the chirality - Yuepeng Qiu; Jiyan Hu; Yao Feng; Yan Ma; Chang Li; Yazhu Liu; Yonghong Lai; Changcai Wu; Ruilong Sun; Ting Tang; Lianshan Li; Fengsong Liu (Pesticide Biochemistry and Physiology, 2026)

Integrating metagenomics analysis and machine learning to identify drivers of antibiotic resistance genes abundance in microplastic-contaminated soil - Yijia Li; Junwei Ma; Xue Li; Ting Ling; Yike Zhang; Xinghui Xia (Journal of Hazardous Materials, 2026)

Rational design of zeolite-based composite catalysts in catalytic cracking of polyethylene - Yan Li; Zhe Ma; Jingyuan Shang; Ting Wang; Xingong Zhang; Peng Xu; Chenzhao Wang; Xiang Feng; De Chen; Chaohe Yang; Xiaobo Chen (Fuel, 2026)

A fluorescence biosensor based on upconversion nanoparticles and metal organic frameworks for multiresidue detection and enrichment of neonicotinoid pesticides - Huan Yun; Honglin Li; Zijie Dou; YuHao Zhang; Ting Guo; Ying Zhou; Hongyuan Zhou; Liang Ma; Xiaozhu Liu (Food Chemistry, 2026)

Elucidating processes and mechanisms of enhanced crude oil degradation by a genomics-guided microbial consortium - Xue Li; Junwei Ma; Yijia Li; Ting Ling; Yike Zhang; Xinghui Xia (Chemical Engineering Journal, 2026)

Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Stochastic assembly of rhizosphere microbial communities drives super rice yield variation via enhanced nutrient metabolism - Qiuyuan Chen; Ye Liu; Zongrun Li; Yimei Wang; Liuhang Wang; Yafan Zhao; Ting Peng; Guohui Ma; Congdang Yang; Quanzhi Zhao; Jing Zhang (Applied Soil Ecology, 2026)

Sustainable tea production in western Sichuan: Defining optimal soil pH threshold to balance rhizosphere bacterial communities and flavor metabolites - Haojie Cao; Ning Ma; Siyu Wang; Ting Li; Zijun Zhou; Shirong Zhang; Yulin Pu; Yongxia Jia; Xiaojing Liu; Xiaoxun Xu; Guiyin Wang (Applied Soil Ecology, 2026)

Enrichment of anthropogenic organic matter and acetoclastic pathway dominates ebullition CH4 production in urban river - Shengnan Wu; Dongqi Wang; Hongmei Ma; Yufang Li; Guanghui Zhao; Hechen Sun; Fanyan Yang; Xin Xu; Ting Liu; Ziqi Ren; Shu Chen; Chenyang Wu; et al. (Water Research, 2025)

Microbial mechanisms of biochar reducing methane emission in a rice-crayfish integrated system - Linjie Ma; Chengxin Zhang; Baoli Qin; Ting Yang; Rong Xu; Lingyu Zhu; Guangming Han; Leiming Wu; Siyu Li; Jianhua Bi; Shouhong Wang; Jiahong Zhang; et al. (Journal of Environmental Management, 2025)

The superiority of non-gastrointestinal hydrolysis in preparing egg white-derived peptides for orally colitis mitigation: Transepithelial transport and microbiota regulation - Sitong Ma; Jingbo Liu; Hui Zhang; Yajuan Li; Boqun Liu; Long Ding; Ting Zhang; Chunmei Liu; Meng Yang; Zhiyang Du (Food Research International, 2025)

Phosphorylated eggshell membrane peptides and proanthocyanidin aggregates could be used as emulsion stabilizers: Structural characterization, molecular interactions, and applications in emulsion products - Weiyi Ma; Jingbo Liu; Metta Cita Andriani; Shengrong Dang; Chenman Li; Qi Yang; Ting Zhang; Siwen Lyu (Food Research International, 2025)

Metal-center boosted adsorption capacity of bimetallic CeBi-metal organic frameworks for electrochemical monitoring of heavy metal ions in environment and food samples - Huimin Ma; Renhui Yang; Zixuan Xu; Quan Yang; Xiaoxian Hu; Yuanyuan Zhang; Ting Zeng; Juan Yang; Caoling Li; Nianjun Yang (Food Chemistry, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

Bacteria-loaded Biochar (BC)/Phosphorus‑Modified Biochar (PBC): An Efficient Biosorbent for Remediation of Cd and Pb Co-Contaminated Soil - Ting Wei; Yuyao Wang; Xiulian Ma; Rongyi Hu; Junkang Guo; Li Hua; Xingkai Zhang (Water, Air, & Soil Pollution, 2025)

Identification of AhFPA1 as the causal gene underlying qEFT13.1, a key QTL for early flowering in peanut - Zhao Li; Yu Liu; Qingliang Hu; Jiahao Liang; Zehua He; Yixin Wang; Wenrui Zhang; Ting Pan; Gonghao Ma; Jing Wang; He Zhang; Zhenghao Lv; et al. (Theoretical and Applied Genetics, 2025)

Mechanism of Axial Chain Rockbursts in Deep Tunnels: Structural Plane-Induced Stress Concentration Triggered by Drilling and Blasting - Hong-Pu Li; Ben-Guo He; Xia-Ting Feng; Wen-Jing Niu; Tao Ma (Rock Mechanics and Rock Engineering, 2025)

SOX11-mediated CBLN2 Upregulation Contributes to Neuropathic Pain through NF-κB-Driven Neuroinflammation in Dorsal Root Ganglia of Mice - Ling-Jie Ma; Tian Wang; Ting Xie; Lin-Peng Zhu; Zuo-Hao Yao; Meng-Na Li; Bao-Tong Yuan; Xiao-Bo Wu; Yong-Jing Gao; Yi-Bin Qin (Neuroscience Bulletin, 2025)
Neuropathic pain, a debilitating condition caused by dysfunction of the somatosensory nervous system, remains difficult to treat due to limited understanding of its molecular mechanisms. Bioinformatics analysis identified cerebellin 2 (CBLN2) as highly enriched in human and murine proprioceptive and nociceptive neurons. We found that CBLN2 expression is persistently upregulated in dorsal root ganglia (DRG) following spinal nerve ligation (SNL) in mice. In addition, transcription factor SOX11 binds to 12 cis -regulatory elements within the Cbln2 promoter to enhance its transcription. SNL also induced SOX11 upregulation, with SOX11 and CBLN2 co-localized in nociceptive neurons. The siRNA-mediated knockdown of Sox11 or Cbln2 attenuated SNL-induced mechanical allodynia and thermal hyperalgesia. High-throughput sequencing of DRG following intrathecal injection of CBLN2 revealed widespread gene expression changes, including upregulation of numerous NF-κB downstream targets. Consistently, CBLN2 activated NF-κB signaling, and inhibition with pyrrolidine dithiocarbamate reduced CBLN2-induced pain hypersensitivity, proinflammatory cytokines and chemokines production, and neuronal hyperexcitability. Together, these findings identified the SOX11/CBLN2/NF-κB axis as a critical mediator of neuropathic pain and a promising target for therapeutic intervention.

Innovative emulsification and freeze-drying techniques for developing heat-resistant chocolates with tunable textures and sensory attributes - Qianqian Li; Lulu Zhang; Xi Zhang; Jie Zhang; Shuaijia Zhang; Ting Xu; Yuhui Wang; Ruyi Geng; Ashraf Nagib; Yilei Li; Yulin Hu; Yuyue Wang; et al. (Food Chemistry, 2025)

Exogenous supplementation of key membrane lipid precursors enhances freeze-drying resistance in Lacticaseibacillus paracasei K56 by modulating membrane composition - Fengzhi Qiao; Xia Ma; Ting Sun; Baolei Li; Shaolei Wang; Shichao Xuan; Pimin Gong; Weilian Hung; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Electronic nose, HS-GC-IMS, HS-SPME-GC-MS, and deep learning model were used to analyze and predict the changes and contents of VOCs in in-shell walnut kernels under different roasting conditions - Kaiyang Zhu; Xinyi Zhang; Ji Ma; Hafiz Muhammad Mubeen; Ting Zhang; Hongjie Lei; Wenge Zhao; Huaide Xu; Mei Li (Food Chemistry, 2025)

Nitrogen transformation in the crop-soil system determines the exacerbation of yield-scaled N2O emissions from rice paddies under climate change - Yuanyuan Wang; Wei Huang; Ziqi Xu; Zhenghua Hu; Tingwu Liu; Guihua Lu; Kezhi Zheng; Dan Dong; Yonggang Xu; Shuqi He; Gecong Ma; Ting Li; et al. (Field Crops Research, 2025)

Dual-gripper coordination effect stabilizing zinc anodes for high-performance zinc metal batteries - Tian-Yi Yang; Kun Li; Ting-Ting Su; Li Ma; Qiu-Shuai Xu; Chang-You Shao; Wen-Feng Ren; Run-Cang Sun (Chemical Engineering Journal, 2025)

Multifunctional ceria nanozyme with dual anti-fungal/anti-MMP activity for glucocorticoid- associated severe fungal keratitis: A transcriptomics- guided design - Shanmei Lyu; Min Yin; Hongwei Wang; Dingwen Cao; Li Ma; Ting Zhang; Chao Wei; Weiyun Shi (Chemical Engineering Journal, 2025)

ROS-triggered self-assembling peptide hydrogel combining bacterial entrapment and intracellular penetration for Salmonella Typhimurium-induced enteritis therapy - Wenwen Meng; Hao Yang; Wenqian Zhang; Xueyan Li; Jiajun Sun; Ting Hu; Wei Li; Yaohong Zhu; Yong Wang; Xi Ma; Guiyan Yang; Jiufeng Wang (Chemical Engineering Journal, 2025)

Chemical fixation of carbon dioxide into bio-debris as sustainable bioplastics - Bailang Zhang; Yongfang Wang; Ting Wang; Dandan Liu; Yuwei Chen; Lan Ma; Mingjie Li; Chaoxu Li (Chemical Engineering Journal, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Cascading effects of tree diversity loss on herbivore-parasitoid interactions - Ming-Qiang Wang; Kai Zhang; Georg Albert; Sylvia Haider; Yi Li; Jing-Ting Chen; Andréa Davrinche; Qing-Song Zhou; Arong Luo; Tobias Proß; Keping Ma; Helge Bruelheide; et al. (Biological Conservation, 2025)

Unveiling hidden threats: Nitrate pollution in agricultural catchments with deep vadose zone - Min Ren; Xining Zhao; Ruxin Shao; Mingyi Wen; Xiaodong Gao; Liuyang Yu; Nanfang Ma; Ting Yang; Jingdan Zhao; Changjian Li (Agriculture, Ecosystems & Environment, 2025)

Evaluating dextrorphan as a wastewater biomarker for cough suppressant use: A longitudinal study in China - Xue-Ting Shao; Xin-Dong Ma; Jing-Long Li; Jake W. O’Brien; Kevin Thomas; De-Gao Wang (Water Research, 2025)

Particulate matter removal performance of basalt fiber fabric: Optimization on the textile structure and surface functionalization - Ming-Cheng Gao; Ting Zhao; Hui Li; Cun-Guang Liang; Xiao-Xi Cheng; Xin Jia; Peng-Cheng Ma (Journal of Environmental Chemical Engineering, 2025)

Preparation of bacterial cellulose-aloe emodin-vanillin eco-friendly composite film for salmon preservation: Antioxidant, antibacterial, and pH-Responsive color change - Xueqing Zhao; Mingbo Yang; Haolong Zheng; Zhiqing Zhao; Mengyue Duan; Ge Gao; Ting Ma; Guoqiang Li (Food Hydrocolloids, 2025)

EpicPCR-based identification of diversity and community structure of environmental alkBs-carrying bacteria - Tianhua Lv; Yunke Cao; Shuai Chen; Wenzhuo Tian; Yuan Yun; Guoqiang Li; Ting Ma (Environmental Research, 2025)

Analyzing public response to wildfires: A socio-spatial study using SIR models and NLP techniques - Zihui Ma; Guangxiao Hu; Ting-Syuan Lin; Lingyao Li; Songhua Hu; Loni Hagen; Gregory B. Baecher (Computers, Environment and Urban Systems, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

Aramid nanofiber-reinforced MXene fibers for flexible supercapacitors - Yiwen Gan; Ningjing Song; Jiaxin Quan; Ting Ding; Xupu Jiang; Rui Wang; Wujun Ma; Chuntao Lan; Min Li; Meifang Zhu (Chemical Engineering Journal, 2025)

Enhancing therapeutic potential of cellular hitchhiking through bioorthogonal chemistry - Jiajia Jia; Maoying Zhang; Aiyang Tong; Ting Fang; Xuerui Ma; Yaying Gao; Jian Zhang; Dongkai Wang; Ji Li (Chemical Engineering Journal, 2025)

Targeting superfast sodium energy of coal-based hard carbon by precise regulation of pseudographitic structure - Yaxin Huang; Zhidong Hou; Jianfang Wang; Yongli Li; Ting Ma; Ying Zhan; Chunguang Wei; Jian-Gan Wang; Ding Nan (Chemical Engineering Journal, 2025)

Divergent drivers of litter decomposition in karst and non-karst tropical rainforests: a comparison - Qi Liu; Xinli Chen; Fuzhao Huang; Jianxing Li; Ting Chen; Fang Lu; Xiankun Li; Dongxing Li; Wusheng Xiang; Bin Wang; Hongming Zhao; Ruixia Ma; et al. (CATENA, 2025)

Shifts in the vegetation and microbial conditions accelerate soil organic carbon accumulation over a 65-year desert revegetation chronosequence - Ting Zhang; Bin Niu; Yongli Wang; Zhifu Wei; Gen Wang; Xueyun Ma; Xinrong Li (CATENA, 2025)

KC1036, a multi-kinase inhibitor with anti-angiogenic activity, can effectively suppress the tumor growth of Ewing sarcoma - Xuejin Ou; Ge Gao; Qizhi Ma; Diyuan Qin; Kai Li; Mingyang Feng; Yu Gao; Yao Zeng; Yue Chen; Xia He; Ting Zhang; Zeming Mo; et al. (Angiogenesis, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

An SNP for the splice donor variant of i-type lysozyme 2 (lyz-i2) is associated with the resistance of Vibrio harveyi in Pacific white shrimp - Xin Zhang; Peng Luo; Chunhua Ren; Pengying Li; Yehui Tan; Hao Yang; Shuyang Wen; Bo Ma; Jiayue Yin; Yanhong Wang; Xiao Jiang; Jingxuan Liang; et al. (Aquaculture, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Towards the digitalization of water treatment facilities: A case study on machine learning-enabled digital twins - Zeyu Ma; Yunyi Zhu; Chunsheng Chen; Ting Li; Yanan Li; Xiaoding Li; Yuan Wang; T. David Waite; Jing Guan (Journal of Water Process Engineering, 2025)

Unveiling the effects of dissolved organic matter on heavy metal(loid)s distribution in the Wujiang cascade reservoirs, China - Hongbo Wang; Yueting Meng; Jiaju Liu; Lei Du; Haotian Ma; Enhang Liang; Bin Li; Ruoqi Ma; Ting Wang (Journal of Hazardous Materials, 2025)

Evolving trends in nanozyme-based SERS systems for food contaminant monitoring: A review - Tianle Wu; Yifei Mao; Ting Wang; Lingxuan Ma; Jiliang Cao; Beibei Xie; Jinchao Wei; Peng Li (Food Chemistry, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Solar-driven Janus fabric evaporator: Efficient desalination and selective lithium enrichment - Hong-Bei He; Yue Ma; Qing-Kai Zhu; Ting-Ting Li; Ching-Wen Lou; Jia-Horng Lin; Hai-Tao Ren (Chemical Engineering Journal, 2025)

Efficiently hydrogenolysis of aromatic ether C-O bonds in lignite and model compounds over carbon-coated NiCo bimetallic catalyst - Caitao Chen; Juan Ma; Yakun Tang; Xiaohui Li; Guangbo Liu; Hanyao Song; Yingluo He; Noritatsu Tsubaki; Lang Liu; Ting Liu (Fuel, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

Preparation and characterization of microcapsules using an acid-tolerant sanxan gum combined with sodium alginate/chitosan and their application in Lactobacillus plantarum delivery - Yue Ming; Zhuangzhuang Shi; Yufei Zhao; Jue Li; Wei Sha; Weilong Wang; Guoqiang Li; Mengmeng Wu; Ting Ma (Carbohydrate Polymers, 2025)

High-quality reference genome and population analysis of allotetraploid Elymus sibiricus provide insight into genome origin and environmental adaptations to the Qinghai-Tibetan Plateau - Xinrui Li; Changbing Zhang; Lili Wang; Gai Huang; Daxu Li; Changmian Ji; Zujun Yang; Minghong You; Lijun Yan; Lili Chen; Wenlong Gou; Xiong Lei; et al. (Science China Life Sciences, 2025)

Integrated transcriptomics and lipidomics reveal mechanisms regulating lipids formation and accumulation in oil body during walnut seed development - Kaiyang Zhu; Yingying Zhang; Ji Ma; Ting Zhang; Hongjie Lei; Wenge Zhao; Huaide Xu; Mei Li (Planta, 2025)

Isotopic disequilibrium of the retro-diffusive CO2 efflux affects photosynthetic C18OO discrimination and the estimation of mesophyll conductance - Sui Min Huang; Jérôme Ogée; Xiao Ying Gong; Wei Ting Ma; Lei Li; Xuming Wang; Hans Schnyder; Rudi Schäufele (Agricultural and Forest Meteorology, 2025)

Source of dietary iron and zinc affects meat quality by altering muscular fatty acid profile, flavor substances, and metabolomics in finishing pigs - Zhimei Tian; Miao Yu; Yiyan Cui; Dun Deng; Min Song; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Meat Science, 2025)

Effects of combination of UV-B irradiation and drying on the physicochemical properties of key components and processing quality of germinated whole wheat flour - Ting Wei; Wentong Liu; Jiahao Huang; Na Ji; Qingjie Sun; Man Li; Meng Ma; Fengwei Xie (Journal of Cereal Science, 2025)

Preparation, structural characterization and in vitro digestibility mechanism of walnut oil body emulsion gels based on crosslinking of edible polysaccharide and vanillin - Kaiyang Zhu; Ji Ma; Hafiz Muhammad Mubeen; Ting Zhang; Hongjie Lei; Wenge Zhao; Huaide Xu; Mei Li (Food Hydrocolloids, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

Mixed-cation engineering of hybrid antimony chlorides for band gap-directing deep-blue emission - Ren-Jie He; Lin-Xia Yang; Xin-Yu Ma; Ting-Jie Wang; Zengsheng Guo; Jinling Miao; Suna Wang; Cuncheng Li; Guang-Ning Liu (Chemical Engineering Journal, 2025)

Holocene Indian Summer monsoon cyclic oscillations revealed by Qionghai Lake sediments and their influence on civilization evolution - Xiaomei Zhang; Gen Wang; Yongli Wang; Zhifu Wei; Ting Zhang; Xueyun Ma; Zelong Li; Xinyu Huang; Shixin Zhou (CATENA, 2025)

A silence catalyst: CCL5-mediated intercellular communication in cancer - Wei-Ting Hu; Ming Li; Pei-Jun Ma; Ding Yang; Xiao-Dong Liu; Yun Wang (Archives of Toxicology, 2025)

Temporal thresholds and depth-specific mechanisms of soil organic carbon stabilization during 65 years of revegetation in the Tengger Desert - Ting Zhang; Bin Niu; Yongli Wang; Zhifu Wei; Gen Wang; Xueyun Ma; Xinrong Li (Journal of Environmental Management, 2025)

Flower like ZnO hybrid mediated visible light harvesting film with upgraded photodynamic antibacterial capacity for effective food preservation - Qingqing Li; Xinjie Yang; Zhiyi Wu; Longdong Qin; Linpin Luo; Liang Zhang; Ting Du; Bingzhi Li; Yiyue Ma; Yuanyuan Cheng; Wenxin Zhu; Wentao Zhang; et al. (Food Chemistry, 2025)

Facile preparation of W/O Pickering emulsion gels stabilized with oleanolic acid for the co-delivery of curcumin and epigallocatechin gallate - Shiqi Liu; Yuhui Wang; Qianqian Li; Shuaijia Zhang; Ting Xu; Lulu Zhang; Chao Ma (Food Chemistry, 2025)

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

Adopting cost-effective restoration portfolios for multi-objective ecosystem service optimization: A case study from Northern Shaanxi, China - Ting Li; Jing Huang; Liyang Ma; Shuhua Zhang; Yanjiao Ren; Yadong Yang (Ecological Engineering, 2025)

Synergistic enhancement of CO2 hydrate synthesis via magnetic stirring coupled with gas bubbling - Xiangxuan Li; Ting Wang; Ting Ma; Qiuwang Wang (Chemical Engineering Journal, 2025)

Performance and mechanism of lead and cadmium stabilization in soil via two types of phosphorus-enriched biochars - Yingying Wu; Haibo Li; Ting Ma; Xinyi Gao; Yicheng Wu; Tianle Zhang (Biocatalysis and Agricultural Biotechnology, 2025)

Light intensity is a crucial factor that regulates growth, physiological traits, antioxidant defense, and metabolite acquisition in Dendrobium denneanum - Hui Wang; Siyu He; Yijun Fan; Ting Li; Linlong Xu; Jie Ma; Junlan Wu; Haolin Liu; XuYang Liu; ChunHong Mou; Meng Zhao; Li Chen; et al. (Physiology and Molecular Biology of Plants, 2025)

Aeromagnetic Compensation Method Based on Recursive Least Square and Elastic Weight Consolidation - Xiao-Yu Ma; Jin-Sheng Zhang; Shou-Yi Liao; Ting Li; Ze-Hao Li (Applied Geophysics, 2025)

First Report of the Molecular Prevalence of Trichomonads from Oral Cavities in Household Dogs and Cats in East China - Li-qin Gui; Xing-hua Wu; Si-lan Shi; Chen-chen Liu; Man-ting Li; Xue-li Ge; Jia-min Ma; Rong-jun Gong; Xin-chao Liu; Wen-chao Li (Acta Parasitologica, 2025)

Biochar-algae microspheres based on sodium alginate for the highly efficient adsorption of malachite green dye: Kinetics, isotherms, and mechanism of adsorption - Wei-Zhe Wu; Rui Li; Zhi-Qian-Li Ma; Chun-Xiao Liu; Wen-Ting Zhao (Journal of Contaminant Hydrology, 2025)

Molecular mechanisms based on peripheral level of vanillin recognition in Orthaga achatina (Lepidoptera: Pyralidae) - Ting-Ting Yang; Yu Ma; Zheng Dai; Ying Li; Ji-Xiang Wang; Teng-Fei Bai; Merid Negash Getahun; George F.O. Obiero; Shuang-Lin Dong; Jin Zhang; Qi Yan (Insect Biochemistry and Molecular Biology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Nb2CTx modulated glycine film with multi-orientational piezoelectricity and photothermal functions designed for biomedical applications - Weiying Zheng; Tong Li; Lili Qian; Juan Ma; Zhibo Liu; Fei Jin; Zhidong Wei; Ting Wang; Zhang-Qi Feng (Chemical Engineering Journal, 2025)

Tribological and wear behavior of alfalfa briquettes during densification: Impact of moisture content - Ting Lei; Yubin Li; Yanhua Ma; Haijun Du; Xiaochen Du (Biomass and Bioenergy, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Mycorrhizal growth and resource exchange define plant’s coexistence - Jiqiong Zhou; Pengsen Wang; Xiangjun Li; Li Wei; Yakov Kuzyakov; Yingying Su; Jianguo Zhang; Nan Huang; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; et al. (Plant and Soil, 2025)

The light-responsive transcription factor SlBBX20 improves low-temperature resistance of Solanum lycopersicum by affecting photosynthetic capacity, antioxidant capacity, and osmotic adjustment - Yongbo Ma; Manling Chen; Yingjin Xing; Zhenglun Li; Ting Zhou; Haijing Yan; Jiahui Yan; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Plant Cell Reports, 2025)

Protective Effect of Lycium Barbarum Polysaccharides and Sodium Selenite on Cadmium Chloride–Induced Testicular Toxicity in Rats - Xueling Zhang; Yongxin Zhang; Ting Wang; Deng Xiao; Jianding Wang; Chao Ma; Tong Liu; Duoming Zhao; Sheng Li; Junling Wang; Chengyun Li (Biological Trace Element Research, 2025)

Disrupted coordination between primary and high-order cognitive networks in Parkinson’s disease based on morphological and functional analysis - Yunxiao Ma; Li Wang; Ting Li; Jian Zhang; Shintaro Funahashi; Jinglong Wu; Xiu Wang; Kai Zhang; Tiantian Liu; Tianyi Yan (Brain Structure and Function, 2025)

Impact of transglutaminase on structural and rheological properties of pea protein-cornmeal-wheat gluten blends for meat analogue production - Xiaowei Yu; Ting Li; Minghui Yue; Shanshan Zhang; Yingjuan Zhang; Xin Wang; Yubin Zhao; Jing Wu; Chenjie Wang; Chengye Ma (Journal of Food Engineering, 2025)

Fructose-modified chitosan-based coassemblies reinforced oral bioavailability of egg white oligopeptides and curcumin via glucose transporter 2-oriented transcytosis and preferable mucus permeation - Jingbo Liu; Yang Liu; Shanglin Li; LongJiang Tian; Yajuan Li; Chunmei Liu; Sitong Ma; Ting Zhang; Meng Yang; Zhiyang Du (Food Research International, 2025)

Combined use of steam explosion, alkali, and microbial methods improving the yield, structure and properties of soluble dietary fiber from bamboo shoot shells - Yu Wang; Jie Tong; Ting Wang; Ruotong Ma; Mariem Elmalki; Dandan Li; Chuang Li; Zhenglian Xue; Xu Fang; Guangjun Nie (Food Chemistry, 2025)

Winter wheat harvest detection via Sentinel-2 MSI images - Jibo Yue; Yihan Yao; Jianing Shen; Ting Li; Nianxu Xu; Haikuan Feng; Yihao Wei; Xin Xu; Yinghao Lin; Wei Guo; Yuanyuan Fu; Hongbo Qiao; et al. (International Journal of Remote Sensing, 2025)

Common immunotoxicity mechanisms of hepatotoxicity induced by raw Polygonum multiflorum and Polygonum multiflorum praeparata: Inhibition of M2 macrophage polarization - Shuaishuai Chen; Taotao Ma; Minmin Hu; Ruixi Li; Dingyan Lu; Yang Jin; Mingliang Zhang; Yong Huang; Yongjun Li; Ting Liu; Wen Liu (Toxicon, 2025)

Synchronous nitrogen and sulfur removal in sulfur-coated iron carbon micro-electrolytic fillers: Exploring the synergy between sulfur autotrophic denitrification and iron-carbon micro-electrolysis - Yanhe Han; Jing Wang; Ting Liu; Mengxiang Wei; Shizong Wang; Jingxuan Guo; Xuejiao Ma; Zaixing Li; Nannan Wang; Yimin Sang (Journal of Hazardous Materials, 2025)

Egg white-derived peptides co-assembly-reinforced zein/chondroitin sulfate nanoparticles for orally colon-targeted co-delivery of quercetin in colitis mitigation - Sitong Ma; Jingbo Liu; Yajuan Li; Yingying Liu; Shanglin Li; Yang Liu; Ting Zhang; Meng Yang; Chunmei Liu; Zhiyang Du (Food Bioscience, 2025)

How to promote sustainable recycling of plastic packaging waste? A study combining machine learning with gaming theory - Shuhan Yang; Ruyin Long; Hong Chen; Jingwen Na; Qingqing Sun; Ting Yue; Qianwen Li; Xinru Wang; Wanqi Ma; Mark Goh (Environmental Impact Assessment Review, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Dual physically crosslinked azobenzene liquid crystal elastomers programmable for multi-modal information encryption - Jia-Xin Yang; Xue-Li Zhang; Lu Yin; Jie Jiang; Ting Liu; Jing-Yu Liu; Zhi-Ting Xu; Hong-Yuan Bai; Hong-Wei Ma; Yue Zhao; Yang Li; Li Han (Chemical Engineering Journal, 2025)

Lake level variability on the Northeastern Tibetan Plateau linked to interaction between Westerlies and Asian monsoon since the last deglaciation - Xueyun Ma; Zhifu Wei; Gen Wang; Ting Zhang; Pengyuan Zhang; Kaikang Liang; Zengguang Guo; Shangkun Li; Xiaomei Zhang; Jianzhen Chen; Zelong Li; Wei He; et al. (CATENA, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Confinement of reactive species in close proximity to pollutants achieves ultrafast advanced oxidation processes in core-shell CoOx@FeOx/pC - Ting Ma; Haibo Li; Yu Shang; Wei Yu; Kaixuan Wang; Rongyu Zhang; Yilin Bai; Xinyi Gao; Xiangqi Nie (Process Safety and Environmental Protection, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Enhancing electrochemical performance in sodium-ion batteries: Strategic modification of oxygen-containing functional groups in hard carbon - Yulong Li; Yin Yang; Rundan Lin; Chen Zhang; Ting Xiao; Zhuang Ma; Qi Zhang; Xinlong Ma (Fuel, 2025)

Directional anchoring of polymer-lysozyme nanohybrids for adhesive capture and enhanced removal of Alicyclobacillus acidoterrestris in fruit juices - Bingzhi Li; Kun Cheng; Lunjie Huang; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Bangfeng Fu; Maojun Jin; et al. (Food Chemistry, 2025)

Responses of soil water supply during the wheat growing season to agricultural management practice in Northern China: A meta-analysis - Lina Jiang; Shuya Li; Huifang zheng; Ting Zhang; Jingwen Li; Bingxin Tian; Jianhui Ma (Field Crops Research, 2025)

Charge density redistribution mechanism in dual-functional electrodes for enhanced the sulfophilic and lithiophilic of Li-S cells - Zeyu Geng; Xiaohan Wang; Junwei Li; Haifei Zhu; Ting Meng; Wencheng Qin; Penghui Wu; Yue Xiang; Fei Ma; Haifeng Zhang (Chemical Engineering Journal, 2025)

Simulating Sugarcane Elongation by a Multi-Parameter Generalized Logistic Model with Meteorological Effect - Guojun Zheng; Pengcheng Ma; Qinlong Wang; Hairong Huang; Ting Luo; Xiang Li; Meixin Yan; Zeping Wang; Guanghu Zhu (Sugar Tech, 2025)

Soil microbial community and chemical properties response to blueberry–soybean intercropping system - Linna Ma; Xiang Li; Zhiping Zhang; Ting Zhang; Haibin Duan; Huichuan Huang; Yixiang Liu; Shusheng Zhu; Youyong Zhu; Yingbin Li (Plant and Soil, 2025)

Dorsal CA1 NECTIN3 Reduction Mediates Early-Life Stress-Induced Object Recognition Memory Deficits in Adolescent Female Mice - Yu-Nu Ma; Chen-Chen Zhang; Ya-Xin Sun; Xiao Liu; Xue-Xin Li; Han Wang; Ting Wang; Xiao-Dong Wang; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2025)

The interactive effect of extreme weather events and PM2.5 on respiratory health among the elderly: a case-crossover study in a high-altitude city - Zhenxu Ning; Yanjun Ma; Shuzhen He; Genshan Li; Ting Xiao; Chunguang Ma; Jing Wu (International Journal of Biometeorology, 2025)

In-situ stripping synthesis of Cu2-xS/g-C3N4 heterojunction with feeble nitrogen vacancy sites for constructing complementary enhanced photo-Fenton-like systems - Zhengxu Kang; Xiaohang Ren; Yun Wang; Jiali Li; Youliang Ma; Zhongmin Feng; Ting Sun (Journal of Water Process Engineering, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Effect of noodle specifications on the quality characteristics of fermented hollow noodles - Hanrui Yang; Jiaying Shang; Chong Liu; Jiasheng Wang; Xuedong Li; Xiaomeng Ma; Jing Hong; Mei Liu; Ting Wang; Binghua Sun; Xueling Zheng (Journal of Cereal Science, 2025)

The global regulator SpoVG is involved in biofilm formation and stress response in foodborne Staphylococcus aureus - Li Xu; Xin Zhang; Wei Wang; Jiawei Shen; Kai Ma; Hui Wang; Ting Xue (International Journal of Food Microbiology, 2025)

Unlocking dual-mode enzyme activities on bacterial surface: Directional recognition and swift capture of Alicyclobacillus acidoterrestris from fruit juices - Bingzhi Li; Kun Cheng; Pengyu Chen; Linpin Luo; Liang Zhang; Ting Du; Tong Zhang; Qingqing Li; Yiyue Ma; Jing Sun; Maojun Jin; Jianlong Wang; et al. (Food Research International, 2025)

Photo-motivated heterojunctions coupling built-in electric field stimulating sulfur redox kinetics for lithium-sulfur batteries - Haifeng Zhang; Fei Ma; Ting Meng; Junwei Li; Haifei Zhu; Zeyu Geng; Wenbo Zhao; Xiaohan Wang; Penghui Wu; Abdelnaby M. Elshahawy; Qianrui Gao; Quande Che (Chemical Engineering Journal, 2025)

Recent progress in MXene fiber: Materials, fabrication techniques, and potential applications - Jiaxin Quan; Xupu Jiang; Ting Ding; Wujun Ma; Min Li; Chuntao Lan; Hengxue Xiang; Wanfei Li; Meifang Zhu; Yuegang Zhang (Chemical Engineering Journal, 2025)

The link between eye movements and cognitive function in mild to moderate Alzheimer’s disease - Xiao-ting Ma; Lin-lin Yao; Shan-wen Liu; Xiao-fen Weng; Run-ying Bao; Yi-fan Yang; Yi-feng Li; Yan-yun Sun; Dan Xu; Zhen-yu Jia; Hua Hu (Experimental Brain Research, 2025)

Environmental safety assessment of cumic acid: A comprehensive study on environmental behaviours and toxicological effects on non-target organisms - Mingxing Yue; Ting Li; Yuan Huang; Bin Zhang; Zhiqing Ma (Science of The Total Environment, 2024)

Vkorc1 polymorphisms of the Norway rats in China: Implications for rodent management and evolutionary origin of anticoagulant resistance mutations - Xiuhui Wang; Xiaohui Ma; Meng Qin; Ting Sun; Dawei Wang; Ning Li; Xiaohui Liu; Meidong Jing; Deng Wang; Ying Song (Science of The Total Environment, 2024)

Ornidazole degradation based on peroxymonosulfate activation induced by oxygen vacancies (OV)-enriched Cu-Co-TiO2: Coexistence of free-radical and non-radical pathways - Xiaofei Qin; Haibo Li; Yanyan Yu; Yue Yang; Kaixuan Wang; Ting Ma; Xiangqi Nie; Yilin Bai; Rongyu Zhang (Process Safety and Environmental Protection, 2024)

Synergistically achieving particulate matter reduction and production performance optimization for zinc electrolysis by ultrasonication coupling anode-coated MnO2 - Yanhui Wang; Lingyu Li; Xiyu Jiang; Haiteng Zhang; Xiaocan Bai; Yuhan Huang; Ting Liu; Yan Tan; Zizhen Ma; Huawei Zhang (Journal of Environmental Chemical Engineering, 2024)

Revealing the formation mechanisms of key flavor components during the fermentation of bamboo shoots by combining flavoromics and metagenomics - Cuiwen Jian; Minghao Sun; Ting Ma; Wenxuan Wang; Beibei Lv; Jinxuan Wang; Xiaochun Su; Shubo Li; Yuan Guo (Food Research International, 2024)

Effect of inoculation with different Eurotium cristatum strains on the microbial communities and volatile organic compounds of Fu brick tea - Yu Xiao; Hui Chen; Yulian Chen; Chi-Tang Ho; Yuanliang Wang; Ting Cai; Shi Li; Jinrong Ma; Tianyang Guo; Liang Zhang; Zhonghua Liu (Food Research International, 2024)

Enhanced ethanol synthesis via CO2 hydrogenation using La-Doped CuFeOx catalysts - Kailong He; Yetong Li; Zhenbo Li; Jie Chen; Li Tan; Ting Qiu; XinGang Li; Xiaoxun Ma; Chengyi Dai (Chemical Engineering Journal, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

8-Br-cGMP suppresses tumor progression through EGFR/PLC γ1 pathway in epithelial ovarian cancer - Min Wu; Chunyan Mu; Huiwen Yang; Yue Wang; Ping Ma; Shibao Li; Zhongcheng Wang; Ting Lan (Molecular Biology Reports, 2024)

Fuzzy adaptive-normalized deep encoder-decoder network: Medium and long-term predictor of temperature and humidity in smart greenhouses - Hui-Jun Ma; Xue-Bo Jin; Zi-Meng Li; Yu-Ting Bai (Computers and Electronics in Agriculture, 2024)

Interleukin-11 drives fibroblast metabolic reprogramming in crystalline silica-induced lung fibrosis - Yujia Xie; Shiyu Yang; Yiju Xu; Pei Gu; Yingdie Zhang; Xiaojie You; Haoyu Yin; Bingxin Shang; Yuxin Yao; Wei Li; Dongming Wang; Ting Zhou; et al. (Science of The Total Environment, 2024)

Corrigendum to “Unraveling non-linear dynamics of biomass, photosynthesis efficiency, and lipid accumulation in Chlorella vulgaris under mixotrophic cultivation” [J. Clean. Prod., 448 (2024) 141692] - Zhuang Li; Ting Yuan; Jinjin Zhao; Canmei Wang; Qun Wei; Xiangmeng Ma; Gairen Yang (Journal of Cleaner Production, 2024)

Biodegradation of polybutylene succinate by an extracellular esterase from Pseudomonas mendocina - Ting Hu; Yujun Wang; Li Ma; Zhanyong Wang; Haibin Tong (International Biodeterioration & Biodegradation, 2024)

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

Single-atom oxide-decorated AuNPs for universal enhancement in SERS detection of pesticide residues - Qi Zhang; Binbin Chen; Qingbian Ma; Zunlong Fang; Shu Li; Xiaoyu He; Yufeng Wang; Xiaohua Qi; Qian Chen; Ting Cai; Lin Zhang; Mingqiang Zou; et al. (Analytica Chimica Acta, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Formation, characterization, and application of natural bioactive phytosterol-based oleogels: A review - Yuhui Wang; Shiqi Liu; Lulu Zhang; Ashraf Nagib; Qianqian Li; Ruyi Geng; Xinyu Yu; Ting Xu; Shuaijia Zhang; Ruoyu Duan; Chao Ma; A.M. Abd El-Aty (Food Chemistry, 2024)

Microbiomic and metabolomic dynamics in chrysanthemum waste at different fermentation stages - Yiyan Cui; Xinyan Ma; Miao Yu; Su Peng; Zhimei Tian; Min Song; Dun Deng; Zhichang Liu; Ting Rong; Zhenming Li; Xianyong Ma (Food Bioscience, 2024)

Ferroptosis promotes valproate-induced liver steatosis in vitro and in vivo - Xinrui Yan; Linfeng Ma; Xue Chen; Jing Ren; Yu Zhai; Ting Wu; Yu Song; Xiaojiao Li; Yingjie Guo (Food and Chemical Toxicology, 2024)

Recyclable UV shielding film with water vapor barrier and antimicrobial properties enabled by in situ polymerization of caffeic acid phenethyl ester - Yan Lyu; Jiongjiong Li; Fangmin Liang; Wencan Ma; Hongxia Liu; Cheng Huang; Jian Jiao; Ting Wu; Guigan Fang (Chemical Engineering Journal, 2024)

Strong, anti-swelling, and biodegradable seaweed-based straws with surface mineralized CaCO3 armor - Yuanpu Liu; Wen Peng; Ting Wei; Yajie Yuan; Xianyu Cao; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Carbohydrate Polymers, 2024)

Composition and metabolic flexibility of hydrocarbon-degrading consortia in oil reservoirs - Yuan Yun; Tianhua Lv; Ziyu Gui; Tianqi Su; Weiwei Cao; Xuefeng Tian; Yu Chen; Shaojing Wang; Zhongjun Jia; Guoqiang Li; Ting Ma (Bioresource Technology, 2024)

Multifunctional bacterial cellulose-bentonite@polyethylenimine composite membranes for enhanced water treatment: Sustainable dyes and metal ions adsorption and antibacterial properties - Xueqing Zhao; Mingbo Yang; Yucheng Shi; Liyuan Sun; Haolong Zheng; Mengmeng Wu; Ge Gao; Ting Ma; Guoqiang Li (Journal of Hazardous Materials, 2024)

Quantifying impacts of livestock production on ecosystem services: Insights into grazing management under vegetation restoration - Ting Li; Weihan Feng; Yihe Lü; Liyang Ma; Yuanxin Liu; Ying Luo; Haibin Liang (Journal of Cleaner Production, 2024)

Exploring the influence of sulfadiazine-induced stress on antibiotic removal and transformation pathway using microalgae Chlorella sp. - Yanfang Ma; Shupeng Lin; Ting Guo; Chunchun Guo; Yitao Li; Yahan Hou; Yongchang Gao; Renjie Dong; Shan Liu (Environmental Research, 2024)

Exploring Research Trend and Hotspots on Oxidative Stress in Ischemic Stroke (2001–2022): Insights from Bibliometric - Nan Jiang; Ting Yang; Hongxia Han; Jing Shui; Miaomiao Hou; Wenyue Wei; Gajendra Kumar; Lijuan Song; Cungen Ma; Xinyi Li; Zhibin Ding (Molecular Neurobiology, 2024)

Effects of GPS flex power on DCBs, ionospheric delays and positioning - Yanjun Du; Yuanxi Yang; Xiaolin Jia; Yan Xiang; Wanqiang Yao; Ting Ma; Qin Li (Advances in Space Research, 2024)

Calcite recrystallization and its impact on speleothem geochemistry - Mei He; Yanjun Cai; Xinnan Zhao; Gang Xue; Yanbin Lu; Xing Cheng; Shouyi Huang; Guozhen Wang; Ruoxin Li; Ting Wang; Le Ma; Yingying Wei; et al. (Sedimentary Geology, 2024)

Deep removal of COS by carbon aerogel in natural gas: Performance and regeneration on K2O-Cu/CA adsorbent at room temperature - Ting Liu; Shengnan Deng; Zishun Li; Xianhong Wang; Yuhan Huang; Yan Tan; Zizhen Ma; Huawei Zhang (Fuel, 2024)

Changes in PI3K/AKT and NRF2/HO-1 signaling expression and intestinal microbiota in bleomycin-induced pulmonary fibrosis - Chenchen Li; Yuxia Cao; Yousheng Peng; Ting Ma; Fanlin Wu; Yongli Hua; Xiuqin Wang; Tong Bai; Yanming Wei; Peng Ji (Food and Chemical Toxicology, 2024)

Optimizing canopy spacing configuration enhances foxtail millet grain yield and water productivity by improving stalk lodging resistance in the North China Plain - Yuanning Zhong; Ting Zhang; Wenjun Qiao; Wenwen Liu; Yunzhou Qiao; Yongpeng Li; Mengyu Liu; Yuzhao Ma; Baodi Dong (European Journal of Agronomy, 2024)

Mining for QTL controlling maize low-phosphorus response genes combined with deep resequencing of RIL parental genomes and in silico GWAS analysis - Bowen Luo; Peng Ma; Chong Zhang; Xiao Zhang; Jing Li; Junchi Ma; Zheng Han; Shuhao Zhang; Ting Yu; Guidi Zhang; Hongkai Zhang; Haiying Zhang; et al. (Theoretical and Applied Genetics, 2024)

Emergence of colistin-resistant Stenotrophomonas maltophilia with high virulence in natural aquatic environments - Ting Zhang; Haiyan Wu; Chenchen Ma; Yidi Yang; Haibei Li; Zhongwei Yang; Shuqing Zhou; Danyang Shi; Tianjiao Chen; Dong Yang; Junwen Li; Min Jin (Science of The Total Environment, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

The improvement of tyrosol bioavailability by encapsulation into liposomes using pH-driven method - Yexuan Yao; Li Ma; Chengwei Yu; Ce Cheng; Hongxia Gao; Teng Wei; Litong Li; Zhiyue Wang; Wei Liu; Zeyuan Deng; Liqiang Zou; Ting Luo (Food Chemistry, 2024)

Metabolites and metabolic pathway analysis of sulfadimidine in carp (Cyprinus carpio) based on UHPLC-Q-orbitrap HRMS - Shuwen Wang; Lihong Xing; Xiaojie Sun; Zhaoxin Li; Tao Ding; Jiyao Wang; Jixing Peng; Haijian Ma; Ting Lin; Qingli Yang (Environmental Research, 2024)

Genome-wide association studies dissect low-phosphorus stress response genes underling field and seedling traits in maize - Bowen Luo; Guidi Zhang; Ting Yu; Chong Zhang; Guohui Yang; Xianfu Luo; Shuhao Zhang; Jianyong Guo; Haiying Zhang; Hao Zheng; Zirui Tang; Qile Li; et al. (Theoretical and Applied Genetics, 2024)

Deleterious variants in RNF111 impair female fertility and induce premature ovarian insufficiency in humans and mice - Chengcheng Song; Yingying Qin; Yan Li; Bingyi Yang; Ting Guo; Wenqing Ma; Dian Xu; Keyan Xu; Fangfang Fu; Li Jin; Yanhua Wu; Shuyan Tang; et al. (Science China Life Sciences, 2024)

A key hub for climate systems: deciphering from Southern Ocean sea surface temperature variability - Ninghong Li; Xufeng Zheng; Ting Su; Xiao Ma; Junying Zhu; Dongdong Cheng (Frontiers in Marine Science, 2024)
The Southern Ocean connects the Pacific, Atlantic, and Indian Oceans, serving as a key hub for the global overturning circulation. The climate of the Southern Ocean is closely linked to the low-latitude equatorial Pacific, as well as the high-latitude regions of the North Atlantic, making it an important component of the global climate system. Due to the interactions of various processes such as atmospheric, oceanic, and ice cover, the Southern Ocean exhibits a complex and variable sea surface temperature structure. Satellite observations indicate that since 1980, the sea surface temperature of the Southern Ocean has been cooling, contrary to the global warming trend. However, due to the relatively short length of satellite observations, the specific mechanisms are not yet clear. Here, we used the EOF method to analyze sea surface temperature data since 1870 (HadISST1 and ERSSTV5), with three main separated modes explaining over 70% of the sea temperature variability. Among them, the first mode shows widespread positive sea surface temperature anomalies in the Southern Ocean, with a time series change consistent with global temperature anomalies, representing a mode of global warming. The second mode corresponds to the Atlantic Multidecadal Oscillation (AMO) but with a lag of approximately 4 years. The third mode is consistent with the variability of the El Niño-Southern Oscillation (ENSO). Furthermore, our study indicates that despite the ongoing global warming since 1980, the negative phase of AMO and positive phase of ENSO may counteract the effects of global warming, leading to an overall cooling trend in the sea surface temperature of the Southern Ocean.

Eco-friendly drinking straws: Navigating challenges and innovations - Yuanpu Liu; Na Li; Xuyang Zhang; Ting Wei; Meng Ma; Qingjie Sun; Man Li; Fengwei Xie (Trends in Food Science & Technology, 2024)

Triclocarban and triclosan promote breast cancer progression in vitro and in vivo via activating G protein-coupled estrogen receptor signaling pathways - Ting-Ting He; Xin Li; Jie-Zhi Ma; Yuan Yang; Shiye Zhu; Jianhua Zeng; Lin Luo; Yu-Long Yin; Lin-Ying Cao (Science of The Total Environment, 2024)

Partially knocking out NtPDK1a/1b/1c/1d simultaneously in Nicotiana tabacum using CRISPR/CAS9 technology results in auxin-related developmental defects - Qian-Wei Ren; Tian-Yao Liu; Hu-Jiao Lan; Zhen-Chao Li; Min-Jun Huang; Ya-Ting Zhao; Yu Chen; Li-Na Liao; Xiao-Han Ma; Jian-Zhong Liu (Plant Science, 2024)

Modified halloysite nanotubes as GRAS nanocarrier for intelligent monitoring and food preservation - Qingqing Li; Yuxin Gong; Ting Du; Liang Zhang; Yiyue Ma; Tong Zhang; Zhiyi Wu; Wentao Zhang; Jianlong Wang (Food Chemistry, 2024)

The influence of unique interfacial networks based on egg white proteins for the stabilization of high internal phase Pickering emulsions: Physical stability and free fatty acid release kinetics - Ting Zhang; Shanglin Li; Meng Yang; Yajuan Li; Sitong Ma; Hui Zhang; Longxiang Li; Xuanting Liu; Jingbo Liu; Zhiyang Du (Food Chemistry, 2024)

Investigating cultivation strategies for enhancing protein content in Auxenochlorella pyrenoidosa FACHB-5 - Qun Wei; Ting Yuan; Zhuang Li; Dan Zhao; Canmei Wang; Gairen Yang; Wangwang Tang; Xiangmeng Ma (Bioresource Technology, 2024)

A Combined Manual Annotation and Deep-Learning Natural Language Processing Study on Accurate Entity Extraction in Hereditary Disease Related Biomedical Literature - Dao-Ling Huang; Quanlei Zeng; Yun Xiong; Shuixia Liu; Chaoqun Pang; Menglei Xia; Ting Fang; Yanli Ma; Cuicui Qiang; Yi Zhang; Yu Zhang; Hong Li; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2024)
We report a combined manual annotation and deep-learning natural language processing study to make accurate entity extraction in hereditary disease related biomedical literature. A total of 400 full articles were manually annotated based on published guidelines by experienced genetic interpreters at Beijing Genomics Institute (BGI). The performance of our manual annotations was assessed by comparing our re-annotated results with those publicly available. The overall Jaccard index was calculated to be 0.866 for the four entity types—gene, variant, disease and species. Both a BERT-based large name entity recognition (NER) model and a DistilBERT-based simplified NER model were trained, validated and tested, respectively. Due to the limited manually annotated corpus, Such NER models were fine-tuned with two phases. The F1-scores of BERT-based NER for gene, variant, disease and species are 97.28%, 93.52%, 92.54% and 95.76%, respectively, while those of DistilBERT-based NER are 95.14%, 86.26%, 91.37% and 89.92%, respectively. Most importantly, the entity type of variant has been extracted by a large language model for the first time and a comparable F1-score with the state-of-the-art variant extraction model tmVar has been achieved. Graphical Abstract

Coastal hypoxia response to the coupling of catastrophic flood, extreme marine heatwave and typhoon: a case study off the Changjiang River Estuary in summer 2020 - Xiao Ma; Qicheng Meng; Dewang Li; Yuanli Zhu; Xiaobo Ni; Dingyong Zeng; Di Tian; Ting Huang; Zhihao Jiang; Haiyan Jin; Feng Zhou (Acta Oceanologica Sinica, 2024)

Four new compounds from fruits of Hypericum patulum Thunb. - Li Jiang; Xue Ma; Yang Wang; Jingyi Xue; Zhilong He; Yushan Nie; Ting Liu; Yong-Lin Wang; Yongjun Li (Natural Product Research, 2024)

Selective breeding in the noble scallop (Chlamys nobilis) for low-temperature resistance to reduce overwintering losses - Chuanxu Zhang; Cheng He; Yizhou Sun; Hongkuan Zhang; Ting Ye; Faxin Liu; Hongyu Ma; Shengkang Li; Huaiping Zheng (Aquaculture, 2024)

Improving flood forecasts capability of Taihang Piedmont basin by optimizing WRF parameter combination and coupling with HEC-HMS - Ting Zhang; Ya Gao; Ping Yu; Jianzhu Li; Ping Feng; Huixin Ma (Theoretical and Applied Climatology, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Labile dissolved organic matter (DOM) and nitrogen inputs modified greenhouse gas dynamics: A source-to-estuary study of the Yangtze River - Jiarui Li; Enhang Liang; Chunfang Deng; Bin Li; Hetong Cai; Ruoqi Ma; Qiang Xu; Jiaju Liu; Ting Wang (Water Research, 2024)

Transformation pathways of the carbon-containing group compounds during municipal sludge pyrolysis treatment - Tianxue Yang; Yi Xiao; Xin Zhao; Dongyang Li; Zhifei Ma; Wenxuan Li; Tiancheng Gong; Ting Zhang; Nannan Huang; Beidou Xi. (Waste Management, 2024)

Simplified estimates of soil nematode body mass using maximum diameter: Insights from large-scale grasslands across China - Quanhui Ma; Yu Zhu; Ying Chen; Wenjia Wu; Xue Qing; Ting Liu; Yibo Li; Yao Wang; Yanan Li; Deli Wang; Jushan Liu; Ling Wang (Soil Biology and Biochemistry, 2024)

Insights into structural and functional regulation of chalcopyrite and enhanced mechanism of reactive oxygen species (ROS) generation in advanced oxidation process (AOP): A review - Kaixuan Wang; Haibo Li; Wei Yu; Ting Ma (Science of The Total Environment, 2024)

Heat storage and release characteristics of a prototype CaCO3/CaO thermochemical energy storage system based on a novel fluidized bed solar reactor - Fuliang Nie; Tianzeng Ma; Qiangqiang Zhang; Zheshao Chang; Ting Ren; Khurshida F. Sayfieva; Mingkai Fu; Xin Li (Journal of Cleaner Production, 2024)

Unraveling non-linear dynamics of biomass, photosynthesis efficiency, and lipid accumulation in Chlorella vulgaris under mixotrophic cultivation - Zhuang Li; Ting Yuan; Jinjin Zhao; Canmei Wang; Qun Wei; Xiangmeng Ma; Gairen Yang (Journal of Cleaner Production, 2024)

Immobilization mechanism of Mn2+ in electrolytic manganese residue using sintered ceramsites prepared by alkali-mechanical-roasting method - Xuan Ke; Xiaohong Chen; Ting Wang; Danni Wang; Shuqi Ma; Jia Li; Shenxu Bao; Zhaohua Jing (Journal of Environmental Chemical Engineering, 2024)

A new insight on the xyl upper operon revealed through genomic investigation strategy - Xuefeng Tian; Shaojing Wang; Peishan Chen; Mingbo Yang; Zhaoying Su; Yue Ming; Guoqiang Li; Ting Ma (International Biodeterioration & Biodegradation, 2024)

Theory-guided unraveling of the mechanism underlying Cu1.0/Mn1.0-ZnO with dual reaction centers for enhanced peroxymonosulfate activation - Kaixuan Wang; Haibo Li; Xiaofei Qin; Ting Ma; Lin Zhu; Chenxi Zhang; Wei Yu; Xulun Zhou (Environmental Research, 2024)

Regulating framework aluminum location towards boosted light olefins generation in ex-situ catalytic pyrolysis of low-density polyethylene - Ting Wang; Xiang Feng; Dong Lin; Yan Li; Jingyuan Shang; Jinqing Zhang; Shuo Li; Yibin Liu; Hui Zhao; Zhe Ma; Xiaobo Chen; Xingong Zhang; et al. (Chemical Engineering Journal, 2024)

Efficient bio-remediation of multiple aromatic hydrocarbons using different types of thermotolerant, ring-cleaving dioxygenases derived from Aeribacillus pallidus HB-1 - Mingchang Li; Lu Cao; Dakun Liu; Tianqi Su; Wei Cheng; Guoqiang Li; Ting Ma (Bioresource Technology, 2024)

Effects of tree density variations on outdoor heritage conservation: Numerical study of an ancient brick city wall with four orientations - Ting Zhang; Changchang Xia; Yan Ma; Ruohan Zhang; Shuai Han; Zhenyi Kong; Shuichi Hokoi; Yonghui Li (Building and Environment, 2024)

Combined effects of copper and cadmium exposure on ovarian function and structure in Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Ting Huang; Qiyu Wei; Xin Yan; Liting Chen; Zhirui Ma; Liming Luo; Jinling Cao; Hongxing Chen; Xinxian Wei; Honglian Tan; Fuyan Chen; et al. (Ecotoxicology, 2024)

Ornidazole degradation by PMS activated by Co-Zr-TiO2 with abundant oxygen vacancies: Performance, mechanism and degradation pathway - Xiaofei Qin; Haibo Li; Kaixuan Wang; Yang Liu; Liuyu Song; Ying Lin; Fuhao Fan; Sihan Li; Ting Ma (Process Safety and Environmental Protection, 2024)

Transcriptomics combined with physiological analysis provided new insights into the Zn enrichment capacity and tolerance mechanism of Dendrobium denneanum Kerr - Yuanyuan Liu; Erya Xu; Yijun Fan; Linlong Xu; Jie Ma; Xuebing Li; Hui Wang; Siyu He; Ting Li; Yujiao Qin; Jingtao Xiao; Aoxue Luo (Plant Science, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

Unravelling hidden threats of water disinfection: Toxicity evaluation and toxic products identification during diclofenac degradation - Ding Pan; Cheng Zhang; Cai-Shan Wang; Peng Zhang; Xin-Yi Jiao; Qian-Ru Ma; Li-Ting Wang; Dai-Jun Li; Li-Ping Li (Environmental Pollution, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

The Effect of Copper–Cadmium Co-Exposure and Hormone Remediation on the Ovarian Transcriptome of Nile Tilapia (Oreochromis niloticus) - Yijie Wu; Liting Chen; Xin Yan; Jun Xiao; Zhirui Ma; Zhanyang Tang; Zhongbao Guo; Liping Li; Guixiang Tong; Honglian Tan; Fuyan Chen; Xinxian Wei; et al. (Fishes, 2024)
The escalating problem of copper (Cu) and cadmium (Cd) pollution in aquatic environments poses a significant threat to the ovarian tissue and reproductive capacity of fish, hindering the development of the aquaculture industry. However, the combined effects of Cu and Cd on fish gonadal development remain unclear. In this study, the fish species Nile tilapia was stressed with rearing water containing 300 μg/L Cu2+ and 100 μg/L Cd2+ for 30 days, followed by an intraperitoneal injection of luteinizing hormone-releasing hormone (LHRH-α) and human chorionic gonadotropin (HCG) at various concentrations. We investigated the ovarian transcriptome profiles before and after injection. Prior to injection, combined treatment with Cu and Cd resulted in reproductive dysfunction and metal ion imbalance in tilapia. Transcriptomic profiling revealed differential gene annotation concentrated in the MAPK signaling pathway and regulation of GTPase activity. Post-injection, all concentrations of LHRH-α and HCG groups showed an upregulated gonadosomatic index (G.S.I) and higher levels of vitellogenin (VTG), gonadotropin-releasing hormone (GnRH), gonadotropin (GTH), and estrogen (E2) in serum compared to the negative control group. Transcriptomic analysis revealed alterations in various ovarian signaling pathways, preliminarily revealing the in vivo molecular mechanisms and differences in LHRH-α and HCG. The findings from this study could help us better understand how to counteract the effects of combined Cu and Cd exposure on tilapia ovarian development, which has significant implications for the Nile tilapia aquaculture industry.

Turbot (Scophthalmus maximus L.) occludin gene performs the anti-inflammatory function in the intestine via the regulations by miR-140-3p in the NF-κB pathway - Xin Cai; Peng Sun; Chengbin Gao; Ting Xue; Le Ma; Chao Li (Aquaculture, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

Opportunities for converting waste plastics into petrochemicals: Process design, multi-objective optimization, and omnidirectional techno-economic-society-environment assessment - Xiaobo Chen; Jinqing Zhang; Zhibo Zhang; Zihao Zhang; Xin Zhou; Yaqi Zheng; Ting Wang; Guoliang Li; Ruzhen Ma; Qi Han; Hao Yan; Yibin Liu; et al. (Journal of Cleaner Production, 2024)

N atoms regulate heterogeneous crystal phase engineering of mesoporous magnetic FexN nanofibers to promote electromagnetic wave dissipation of magnetic composite aerogel absorbers - Wanjia Li; Wangchang Li; Zengbao Ma; Yue Kang; Ting Zou; Yu Lei; Yao Ying; Wenbo Xiang; Jing Yu; Jingwu Zheng; Liang Qiao; Juan Li; et al. (Chemical Engineering Journal, 2024)

Hydrophobic, elastic Cyclodextrin-based aerogel with stable broadband sound absorption - Jia-Xin Wang; Haoran Xu; Jun-Feng Feng; Shu-Ting Fan; Min Tan; Li Ma; Bang-Jing Li; Sheng Zhang (Chemical Engineering Journal, 2024)

Hydrogel sensors for biomedical electronics - Jingyun Ma; Jiaqi Zhong; Fuqin Sun; Botao Liu; Zhaoxiang Peng; Jiangfang Lian; Xiang Wu; Lianhui Li; Mingming Hao; Ting Zhang (Chemical Engineering Journal, 2024)

The road to reuse of walnut by-products: A comprehensive review of bioactive compounds, extraction and identification methods, biomedical and industrial applications - Kaiyang Zhu; Ji Ma; Junzhao Cong; Ting Zhang; Hongjie Lei; Huaide Xu; Zisheng Luo; Mei Li (Trends in Food Science & Technology, 2024)

A novel double-network hydrogel made from electrolytic manganese slag and polyacrylic acid-polyacrylamide for removal of heavy metals in wastewater - Mengyu Ma; Xuan Ke; Ting Wang; Jia Li; Hengpeng Ye (Journal of Hazardous Materials, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Arbuscular mycorrhizae mitigate negative impacts of soil biodiversity loss on grassland productivity - Jiqiong Zhou; Yingying Su; Xiangjun Li; Yakov Kuzyakov; Pengsen Wang; Jinchao Gong; Xuxu Li; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2024)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Effects of arsenic exposure on trace element levels in the hippocampus and cortex of rats and their gender differences - Xi Yan; Jun Zhang; Junyu Li; Xinglai Zhang; Yi Wang; Xiaolu Chen; Peng Luo; Ting Hu; Xueshan Cao; Hongbin Zhuang; Xiaoxiao Tang; Fang Yao; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Enhanced expression of RAGE/NADPH oxidase signaling pathway and increased level of oxidative stress in brains of rats with chronic fluorosis and the protective effects of blockers - Yan-Lin Ma; Jie Deng; Ting Zhang; Hong-Mei Li; Qiu-Zhe Liang; Kai-Lin Zhang (Journal of Trace Elements in Medicine and Biology, 2023)

Integrated multifunctional nanoplatform for fluorescence detection and inactivation of Staphylococcus aureus - Jing-bo Jiao; Qing Kang; Jiang-li Cao; Shuai-qi Zhang; Chen-jing Ma; Tong Lin; Ze-hui Xiao; Chu-min Zhao; Ting Du; Xin-jun Du; Shuo Wang (Food Chemistry, 2023)

Screening and genome analysis of lactic acid bacteria with high exopolysaccharide production and good probiotic properties - Jing Lu; Yunren Mao; Ting Ma; Xiaoling Liu; Xiyao Cheng; Yunxia Bai; Shubo Li (Food Bioscience, 2023)

Metabolome and Transcriptome Association Analysis Reveals the Link Between Pigmentation and Nutrition Utilization in the Juveniles of Sea Cucumber Holothuria leucospilota - Jiasheng Huang; Zixuan E; Wenjie Pan; Zhi Li; Tiehao Lin; Chunhua Ren; Peng Luo; Bo Ma; Yang Liu; Xugan Wu; Chaoqun Hu; Xiao Jiang; et al. (Marine Biotechnology, 2023)

Phytoplankton interspecific interactions modified by symbiotic fungi and bacterial metabolites under environmentally relevant hydrogen peroxide concentrations stress - Zhe Li; Hua Ma; Zhicheng Hong; Ting Zhang; Mingxing Cao; Fuyi Cui; Hans-Peter Grossart (Water Research, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Urban vegetation cooling capacity was enhanced under rapid urbanization in China - Chengcong Wang; Zhibin Ren; Yunxia Du; Yujie Guo; Peng Zhang; Guodong Wang; Shengyang Hong; Zijun Ma; Wenhai Hong; Ting Li (Journal of Cleaner Production, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Targeted control of soil erosion through selective regulation of Eleocharis yokoscensis using mixed endophytes - Qifeng Gao; Xiao Xiao; Ting Liu; Zhong Ren; Wei Ren; Yunya Zhan; Wenqian Wang; Weiran Feng; Li Ma; Le Qi; Zixian Zhang; Xubiao Luo; et al. (CATENA, 2023)

Assessment of HCHO in Beijing during 2009 to 2020 using satellite observation and numerical model: Spatial characteristic and impact factor - Jiachen Fan; Tijian Wang; Qingeng Wang; Danyang Ma; Yasong Li; Minqiang Zhou; Ting Wang (Science of The Total Environment, 2023)

Roles of dissolved organic matter (DOM) in shaping the distribution pattern of heavy metal in the Yangtze River - Enhang Liang; Jiarui Li; Bin Li; Shufeng Liu; Ruoqi Ma; Shanqing Yang; Hetong Cai; Zehuan Xue; Ting Wang (Journal of Hazardous Materials, 2023)

HMDB: A curated database of genes involved in hydrocarbon monooxygenation reaction with homologous genes as background - Shaojing Wang; Yuan Yun; Xuefeng Tian; Zhaoying Su; Zitong Liao; Guoqiang Li; Ting Ma (Journal of Hazardous Materials, 2023)

Bismuth oxychloride microsphere-assisted construction of bacterial consortia for enhanced petroleum hydrocarbon degradation under high-salt stress - Zhaoying Su; Yunke Cao; Mingchang Li; Yu Chen; Guoqiang Li; Qilin Yu; Ting Ma (Chemical Engineering Journal, 2023)

Single-molecule recognition of Nucleolin and the interactions with DNA/RNA G-quadruplexes via nanopore decoding - Zhong Wang; Fupeng Qin; Ji Wu; Wenhao Ma; Rongjie Li; Ting Weng; Bohua Yin; Liang Wang; Deqiang Wang; Liyuan Liang (Chemical Engineering Journal, 2023)

Tree communities and functional traits determine herbivore compositional turnover - Ming-Qiang Wang; Zhixin Wen; Jinzhao Ke; Douglas Chesters; Yi Li; Jing-Ting Chen; Arong Luo; Xiaoyu Shi; Qing-Song Zhou; Xiao-Juan Liu; Keping Ma; Helge Bruelheide; et al. (Oecologia, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Characterization of sandalwood (E,E)-α-farnesene synthase whose overexpression enhances cold tolerance through jasmonic acid biosynthesis and signaling in Arabidopsis - Xinhua Zhang; Xiaohong Chen; Jaime A. Teixeira da Silva; Ting Zhang; Yuping Xiong; Yuan Li; Yunfei Yuan; Xiaoping Pan; Guohua Ma (Planta, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

In vitro fermentation characteristics of oxidized konjac glucomannan and its modulation effects on gut microbiota - Yao Li; Ting Gong; Hongjia Lu; Senquan Ma; Xiong Liu (Food Hydrocolloids, 2023)

Hierarchically porous graphene-like biochar for efficient removal of aromatic pollutants and their structure-performance relationship: A combined experimental, MD and DFT study - Shujian Liu; Zhongmin Feng; Youliang Ma; Jiali Li; Yun Wang; Ting Sun (Environmental Pollution, 2023)

Performance of heavy metal-immobilizing bacteria combined with biochar on remediation of cadmium and lead co-contaminated soil - Ting Wei; Han Gao; Fengqiu An; Xiulian Ma; Li Hua; Junkang Guo (Environmental Geochemistry and Health, 2023)

Hsa-miR-195-5p Inhibits Autophagy and Gemcitabine Resistance of Lung Adenocarcinoma Cells via E2F7/CEP55 - Linhai Fu; Zhupeng Li; Yuanlin Wu; Ting Zhu; Zhifeng Ma; Lingjun Dong; Jianyi Ding; Chu Zhang; Guangmao Yu (Biochemical Genetics, 2023)

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

Hypothermic neuroprotection by targeted cold autologous blood transfusion in a non-human primate stroke model - Jian Chen; Shuaili Xu; Hangil Lee; Longfei Wu; Xiaoduo He; Wenbo Zhao; Mo Zhang; Yanhui Ma; Yuchuan Ding; Yongjuan Fu; Chuanjie Wu; Ming Li; et al. (Science Bulletin, 2023)

Engineering oxygen vacancies of 2D WO3 for visible-light-driven benzene hydroxylation with dioxygen - Tao Chen; Fangpei Ma; Zhe Chen; Menglin Xie; Ting Li; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2023)

Long-term drying trends since the mid-Holocene in the Qaidam Basin - Ting Zhang; Gen Wang; Yongli Wang; Zhifu Wei; Wei He; Xueyun Ma; He Ma; Xiaoli Yu; Pengyuan Zhang; Shangkun Li; Jingyi Wei; Lun Li (CATENA, 2023)

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Machine learning algorithm inversion experiment and pollution analysis of water quality parameters in urban small and medium-sized rivers based on UAV multispectral data - Yikai Hou; Anbing Zhang; Rulan Lv; Yanping Zhang; Jie Ma; Ting Li (Environmental Science and Pollution Research, 2023)

The catalytic oxidation process of atrazine by ozone microbubbles: Bubble formation, ozone mass transfer and hydroxyl radical generation - Ting Liu; Bin Zhang; Wenqian Li; Boda Li; Ziwen Han; Yanjie Zhang; An Ding; Shutao Wang; Jun Ma; Xu He (Chemosphere, 2023)

Regulation of Hippo/YAP signaling pathway ameliorates cochlear hair cell injury by regulating ferroptosis - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Xiaoyan Ma; Ting Zhang; Baiya Li; Xudong Ma (Tissue and Cell, 2023)

A seminal perspective on the role of chondroitin sulfate in biomineralization - Jia-xin Hao; Qian-qian Wan; Zhao Mu; Jun-ting Gu; Wei-wei Yu; Wen Qin; Yu-tao Li; Chen-yu Wang; Yu-xuan Ma; Kai Jiao; Franklin Tay; Lina Niu (Carbohydrate Polymers, 2023)

Retraction Note to: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2023)

CO2 improves the anaerobic biodegradation intensity and selectivity of heterocyclic hydrocarbons in heavy oil - Lu Zhang; Xiangyu Zhou; Chuxiao Hu; Shun Yao; Lei Shi; Tong Niu; Xin Li; Lihua Tong; Jiaqiang Zhang; Ting Ma; Wenjie Xia (Environmental Research, 2023)

Viscosity-triggered near-infrared fluorescence nanoprobe for in vivo non-invasive diagnosis of cancer - Wen-Juan Fu; Jian Ting Li; Wen Hui Qian; Xiang Ying Zhang; Dan Dan Ma; Yu Ting Wang; Qi Jia Zhang; Dong Zhu (Chemical Engineering Journal, 2023)

Links between geochemical weathering on the NE Tibetan Plateau and global climate change since the Last Deglacial - Xueyun Ma; Zhifu Wei; Yongli Wang; Gen Wang; Ting Zhang; Wei He; Xiaoli Yu; He Ma; Pengyuan Zhang; Shangkun Li; Qiaohui Fan (CATENA, 2023)

Two new chemical constituents from the leaves of Illicium dunnianum - Jun-Ran Shao; Sen-Ju Ma; Ting Li; Xiao-Qing He; Zhen-Zhong Wang; Wei Xiao; Xin-Sheng Yao; Hai-Bo Li; Yang Yu (Natural Product Research, 2023)

Calcium isotopic geochemistry of geothermal systems in the tectonically active southeastern Tibetan Plateau - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; Jun Zhong; Ting-Ting Ma; Jian Sun; Wen-Yan He; Cong-Qiang Liu (Science of The Total Environment, 2023)

Remediation and its biological responses to Cd(II)-Cr(VI)-Pb(II) multi-contaminated soil by supported nano zero-valent iron composites - Yi Jin; Yaxuan Wang; Xi Li; Ting Luo; Yongsong Ma; Bing Wang; Hong Liang (Science of The Total Environment, 2023)

Sb2Te3 hexagonal nanoplates as conversion-alloying anode materials for superior potassium-ion storage via physicochemical confinement effect of dual carbon matrix - Shaokun Chong; Shuangyan Qiao; Lingling Yuan; Qianwen Zhou; Ting Li; Shihong Dong; Yikun Wang; Meng Ma; Wei Huang (Chemical Engineering Journal, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Effects of combined remediation of pre-ozonation and bioaugmentation on degradation of benzo[a]pyrene and microbial community structure in soils - Xueqin Lu; Ting Luo; Xi Li; Yaxuan Wang; Yongsong Ma; Bing Wang (Environmental Science and Pollution Research, 2023)

Simple and sensitive electrochemical detection of sunset yellow and Sudan I in food based on AuNPs/Zr-MOF-Graphene - Ruimeng Sun; Ruijuan Lv; Yuhan Li; Ting Du; Lixia Chen; Yang Zhang; Xiaoyu Zhang; Lina Zhang; Hainan Ma; Haolin Sun; Yanfei Qi (Food Control, 2023)

Sustained-release antibacterial gelatin films: Effects of diatomite/carvacrol complex on their structure, physicochemical and antibacterial properties - Hejun Wu; Ling Ma; Sen Li; Jie Wang; Ting Li; Lu Peng; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang; Yuntao Liu (Food Packaging and Shelf Life, 2023)

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

Bioleaching and immobilizing of copper and zinc using endophytes coupled with biochar-hydroxyapatite: Bipolar remediation for heavy metals contaminated mining soils - Weiran Feng; Xiao Xiao; Junjie Li; Qicheng Xiao; Li Ma; Qifeng Gao; Yuke Wan; Yutian Huang; Ting Liu; Xubiao Luo; Shenglian Luo; Guisheng Zeng; et al. (Chemosphere, 2023)

High-precision early warning system for rice cadmium accumulation risk assessment - Huili Yan; Hanyao Guo; Ting Li; Hezifan Zhang; Wenxiu Xu; Jianyin Xie; Xiaoyang Zhu; Yijun Yu; Jian Chen; Shouqing Zhao; Jun Xu; Minjun Hu; et al. (Science of The Total Environment, 2023)

Facultative anaerobic conversion of lignocellulose biomass to new bioemulsifier by thermophilic Geobacillus thermodenitrificans NG80-2 - Mingchang Li; Jiaqi Yu; Lu Cao; Yujun Yin; Zhaoying Su; Shuai Chen; Guoqiang Li; Ting Ma (Journal of Hazardous Materials, 2023)

Behaviour of Sr, Ca, and Mg isotopes under variable hydrological conditions in high-relief large river systems - Bei-Bei Chen; Si-Liang Li; Philip A.E. Pogge von Strandmann; David J. Wilson; Jun Zhong; Ting-Ting Ma; Jian Sun; Cong-Qiang Liu (Geochimica et Cosmochimica Acta, 2023)

Review on adsorbents in elemental mercury removal in coal combustion flue gas, smelting flue gas and natural gas - Ting Liu; Zhuo Xiong; Peng Ni; Zizhen Ma; Yan Tan; Zishun Li; Shengnan Deng; Yincui Li; Qirong Yang; Huawei Zhang (Chemical Engineering Journal, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Joint role of land cover types and microbial processing on molecular composition of dissolved organic matter in inland lakes - Zhicheng Hong; Hua Ma; Ting Zhang; Qianru Wang; Yilin Chang; Yingyue Song; Zhe Li; Fuyi Cui (Science of The Total Environment, 2023)

GWAS-assisted genomic prediction of cadmium accumulation in maize kernel with machine learning and linear statistical methods - Huili Yan; Hanyao Guo; Wenxiu Xu; Changhua Dai; Wilson Kimani; Jianyin Xie; Hezifan Zhang; Ting Li; Feng Wang; Yijun Yu; Mi Ma; Zhuanfang Hao; et al. (Journal of Hazardous Materials, 2023)

Exploring cost-effective measure portfolios for ecosystem services optimization under large-scale vegetation restoration - Ting Li; Yihe Lü; Liyang Ma; Pengfei Li (Journal of Environmental Management, 2023)

Genes associated with desiccation stress in foodborne Staphylococcus aureus as revealed by transposon insertion mutagenesis - Hui Wang; Kai Ma; Jiawei Shen; Mengcheng Fang; Hao Pei; Yun Li; Chengfeng Zhu; Fang Shu; Bingbing Li; Ting Xue (Food Research International, 2023)

A novel slag composite for the adsorption of heavy metals: Preparation, characterization and mechanisms - Mengyu Ma; Ting Wang; Xuan Ke; Yanchang Liu; Yunjie Song; Xiaojie Shang; Jia Li; Qingwen Han (Environmental Research, 2023)

A thin LiGa alloy layer from in-situ electroreduction to suppress anode dendrite formation in lithium-sulfur pouch cell - Rong Li; Liwen Yang; Lei Song; Changan Zhou; Jiayu Zhou; Ting Chen; Chen Wu; Yujia Zeng; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

The Nucleus Accumbens CRH–CRHR1 System Mediates Early-Life Stress-Induced Sleep Disturbance and Dendritic Atrophy in the Adult Mouse - Ting Wang; Yu-Nu Ma; Chen-Chen Zhang; Xiao Liu; Ya-Xin Sun; Hong-Li Wang; Han Wang; Yu-Heng Zhong; Yun-Ai Su; Ji-Tao Li; Tian-Mei Si (Neuroscience Bulletin, 2023)

High Fe and Mn groundwater in the Nanchang, Poyang Lake Basin of China: hydrochemical characteristics and genesis mechanisms - Xiaodong Chu; Zhifei Ma; Daishe Wu; Hao Wang; Jingyuan He; Ting Chen; Ziyin Zheng; Hugang Li; Peng Wei (Environmental Monitoring and Assessment, 2023)

Facile one-step synthesis of PhC2Cu nanowires with enhanced photocatalytic performance - Gao-yu Zhao; Hai-yan Li; Yu Yang; Qing-hua Zhao; Ting-ting Su; Jiang-li Ma (Environmental Science and Pollution Research, 2022)

Canagliflozin mitigates ferroptosis and ameliorates heart failure in rats with preserved ejection fraction - Sai Ma; Li-Li He; Guo-Rui Zhang; Qing-Juan Zuo; Zhong-Li Wang; Jian-Long Zhai; Ting-Ting Zhang; Yan Wang; Hui-Juan Ma; Yi-Fang Guo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
Recently, hypoglycemic drugs belonging to sodium-glucose cotransporter 2 inhibitors (SGLT2i) have generated significant interest due to their clear cardiovascular benefits for heart failure with preserved ejection fraction (HFpEF) since there are no effective drugs that may improve clinical outcomes for these patients over a prolonged period. But, the underlying mechanisms remain unclear, particularly its effects on ferroptosis, a newly defined mechanism of iron-dependent non-apoptotic cell death during heart failure (HF). Here, with proteomics, we demonstrated that ferroptosis might be a key mechanism in a rat model of high-salt diet-induced HFpEF, characterized by iron overloading and lipid peroxidation, which was blocked following treatment with canagliflozin. Data are available via ProteomeXchange with identifier PXD029031. The ferroptosis was evaluated with the levels of acyl-CoA synthetase long-chain family member 4, glutathione peroxidase 4, ferritin heavy chain 1, transferrin receptor, Ferroportin 1, iron, glutathione, malondialdehyde, and 4-hydroxy-trans-2-nonenal. These findings highlight the fact that targeting ferroptosis may serve as a cardioprotective strategy for HFpEF prevention and suggest that canagliflozin may exert its cardiovascular benefits partly via its mitigation of ferroptosis.

Development of molecular markers based on CRa gene sequencing of different clubroot disease-resistant cultivars of Chinese cabbage - Ting Lei; Ning Li; Jinjian Ma; Maixia Hui; Limin Zhao (Molecular Biology Reports, 2022)

Pelagic cyanobacterial nitrogen fixation in lakes and ponds of different latitudinal zones - Yan Li; Ye-Xin Yu; Shuo-Nan Ma; Rui-Ting Qiao; Yong-De Cui; Hai-Jun Wang; Hong-Zhu Wang (Aquatic Sciences, 2022)

Isolation and characterization of AaZFP1, a C2H2 zinc finger protein that regulates the AaIPPI1 gene involved in artemisinin biosynthesis in Artemisia annua - Yin-ai Deng; Li Li; Qian Peng; Ling-fang Feng; Jin-fen Yang; Ruo-ting Zhan; Dong-ming Ma (Planta, 2022)

Plant miR167e-5p promotes 3T3-L1 adipocyte adipogenesis by targeting β-catenin - Ting Chen; Fei Ma; Yongjia Peng; Ruiping Sun; Qianyun Xi; Jiajie Sun; Jin Zhang; Yongliang Zhang; Meng Li (In Vitro Cellular & Developmental Biology - Animal, 2022)

Two new chemical constituents from the rhizomes of Actaea dahurica - Sen-Ju Ma; Hai-Bo Li; Jun-Ran Shao; Qian-Qian Pang; Ting Li; Xin-Sheng Yao; Yang Yu (Natural Product Research, 2022)

The shift in temperature zone boundaries in China based on the changes of the climate growing season in the Qinling Mountains from 1964 to 2015 - Chenhui Deng; Hongying Bai; Ting Zhao; Xinping Ma; Wenzheng Li; Meilin Xie (Theoretical and Applied Climatology, 2022)

Modular-level alterations of single-subject gray matter networks in schizophrenia - Yuxiang Guo; Yunxiao Ma; GongShu Wang; Ting Li; Tong Wang; Dandan Li; Jie Xiang; Tianyi Yan; Bin Wang; Miaomiao Liu (Brain Imaging and Behavior, 2022)

Genetic and genomic characterization of multidrug resistant Bacillus subtilis M3 isolated from an activated sludge reactor treating wastewater - Hafeez Ul Haq; Wei Huang; Ye Li; Ting Zhang; Shaocheng Ma; Yajing Zhang; Yongkang Song; Daiyan Lin; Baoyu Tian (Biologia, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Optimizing Fertilizer Management Based on Controlled-Release Fertilizer to Improve Yield, Quality, and Reduce Fertilizer Application on Apples - Junyin Li; Yan Liu; Yafu Tang; Junfei Shao; Ting Xu; Ronghui Ma; Yuanmao Jiang; Dongdong Cheng (Journal of Soil Science and Plant Nutrition, 2022)

Fine mapping and candidate gene analysis of qGSN5, a novel quantitative trait locus coordinating grain size and grain number in rice - Hua Yuan; Peng Gao; Xiaoling Hu; Min Yuan; Zhengyan Xu; Mengya Jin; Wencheng Song; Shijie Zhan; Xiaobo Zhu; Bin Tu; Ting Li; Yuping Wang; et al. (Theoretical and Applied Genetics, 2022)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Resting-state abnormalities in functional connectivity of the default mode network in autism spectrum disorder: a meta-analysis - Qing Wang; Hua-Yun Li; Yun-Da Li; Ya-Ting Lv; Hui-Bin Ma; An-Feng Xiang; Xi-Ze Jia; Dong-Qiang Liu (Brain Imaging and Behavior, 2021)

Investigation of brain damage mechanism in middle cerebral artery occlusion/reperfusion rats based on i-TRAQ quantitative proteomics - Quantao Ma; Chunguo Wang; Min Wang; Yaqi Li; Pengfei Li; Jingkang Wang; Long Cheng; Yongcheng An; Hongyu Dai; Yuhui Duan; Ting Wang; Baosheng Zhao (Experimental Brain Research, 2021)

Mass spectrometry-based proteomic analysis of potential infectious bursal disease virus VP3-interacting proteins in chicken embryo fibroblasts cells - Sun-Ting Ma; Yong-Shan Wang; Xiao-Li Wang; Xing-Xia Xia; Zhen-Wei Bi; Jing-Yu Wang; Yu-Mei Zhu; Wei Ouyang; Jing Qian (Virus Genes, 2021)

Reactive oxygen species altering the metabolite profile of the marine-derived fungus Dichotomomyces cejpii F31-1 - Sharpkate Shaker; Ting-Ting Sun; Liang-Yue Wang; Wen-Zhe Ma; Dong-Lan Wu; Yong-Wei Guo; Jun Dong; Yan-Xiu Chen; Long-Ping Zhu; De-Po Yang; Hou-Jin Li; Wen-Jian Lan (Natural Product Research, 2021)

Temperature-controlled molecular weight of hyaluronic acid produced by engineered Bacillus subtilis - Yingying Li; Zhuangzhuang Shi; Yuzhe Shao; Mengmeng Wu; Guoqiang Li; Ting Ma (Biotechnology Letters, 2021)

Characteristics of the potential vorticity and its budget in the surface layer over the Tibetan plateau - Chen Sheng; Guoxiong Wu; Yiqiong Tang; Bian He; Yongkun Xie; Tingting Ma; Ting Ma; Jinxiao Li; Qing Bao; Yimin Liu (International Journal of Climatology, 2021)
The variability of interior atmospheric potential vorticity (PV) is linked with PV generation at the Earth's surface. The present paper reveals the features of the surface PV and provides a stepping stone to investigate the surface PV budget. In this study, the formats of the PV and PV budget adopting a generalized vertical coordinate were theoretically examined to facilitate the calculation of the surface PV and its budget. Results show that the formats of the PV and PV budget equations are independent of the vertical coordinate. While the vertical component of the surface PV dominates over the platform of the Tibetan Plateau, the horizontal component plays an important role over the slopes of the Tibetan Plateau, especially the southern slope owing to the strong in‐situ meridional gradient of the potential temperature. These results indicate that the employment of complete surface PV not only provides a finer PV structure but also more appropriately reveals its effect on atmospheric circulation. Diagnosis based on reanalysis and model output demonstrates that the surface PV budget equation is well balanced both in terms of the climate mean and synoptic process, and the surface PV budget in June has a prominent diurnal cycle. The diabatic heating with a minimum in the early morning and a maximum from evening to midnight contributes dominantly to this diurnal cycle. It is further indicated that positive PV generation due to diabatic heating is essential for the formation, development, and movement of the Tibetan Plateau vortex.

Chemical composition, antioxidant, antibacterial and cholinesterase inhibitory activities of three Juniperus species - Yujia Zhang; Dong Wu; Shun Kuang; Mingliang Qing; Yue Ma; Tong Yang; Ting Wang; Dengwu Li (Natural Product Research, 2020)

YAP/TAZ affects the development of pulmonary fibrosis by regulating multiple signaling pathways - Ting Zhu; Zhifeng Ma; Haiyong Wang; Xiaoxiao Jia; Yuanlin Wu; Linhai Fu; Zhupeng Li; Chu Zhang; Guangmao Yu (Molecular and Cellular Biochemistry, 2020)

Lycium barbarum polysaccharide protects against Homocysteine-induced Vascular smooth muscle cell proliferation and phenotypic transformation via PI3K/Akt pathway - Minghao Zhang; Fan Li; Smritee Pokharel; Ting Ma; Xiuyu Wang; Yiyong Wang; Weirong Wang; Rong Lin (Journal of Molecular Histology, 2020)

JAB1 promotes palmitate-induced insulin resistance via ERK pathway in hepatocytes - Yun Zhao; Suxian Ma; Xingna Hu; Min Feng; Rong Xiang; Min Li; Chenxiao Liu; Ting Lu; Aijie Huang; Jiaqi Chen; Mian Wu; Honghong Lu (Journal of Physiology and Biochemistry, 2020)

Graph-based network analysis of resting-state fMRI: test-retest reliability of binarized and weighted networks - Jie Xiang; Jiayue Xue; Hao Guo; Dandan Li; Xiaohong Cui; Yan Niu; Ting Yan; Rui Cao; Yao Ma; Yanli Yang; Bin Wang (Brain Imaging and Behavior, 2020)

Gene transfer and nucleotide sequence evolution by Gossypium cytoplasmic genomes indicates novel evolutionary characteristics - Ting-Ting Zhang; Heng Liu; Qi-Yuan Gao; Ting Yang; Jian-Ni Liu; Xiong-Feng Ma; Zhong-Hu Li (Plant Cell Reports, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

High-carbohydrate diet promotes the adaptation to acute hypoxia in zebrafish - Qiang Ma; Chun-Ting Hu; Junjiayu Yue; Yuan Luo; Fang Qiao; Li-Qiao Chen; Mei-Ling Zhang; Zhen-Yu Du (Fish Physiology and Biochemistry, 2020)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Metabolomics and physiological analyses reveal β-sitosterol as an important plant growth regulator inducing tolerance to water stress in white clover - Zhou Li; Bizhen Cheng; Bin Yong; Ting Liu; Yan Peng; Xinquan Zhang; Xiao Ma; Linkai Huang; Wei Liu; Gang Nie (Planta, 2019)

The Rho kinase inhibitor fasudil attenuates Aβ1–42-induced apoptosis via the ASK1/JNK signal pathway in primary cultures of hippocampal neurons - Ye Gao; Yuqing Yan; Qingli Fang; Nianping Zhang; Gajendra Kumar; Jihong Zhang; Li-Juan Song; Jiezhong Yu; Linhu Zhao; Han-Ting Zhang; Cun-Gen Ma (Metabolic Brain Disease, 2019)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Flood scaling under nonstationarity in Daqinghe River basin, China - Jianzhu Li; Qiushuang Ma; Yu Tian; Yuming Lei; Ting Zhang; Ping Feng (Natural Hazards, 2019)

Comparison of volatile profiles and bioactive components of sun-dried Pu-erh tea leaves from ancient tea plants on Bulang Mountain measured by GC-MS and HPLC - Wen-jie Zhang; Cong Liu; Rui-juan Yang; Ting-ting Zheng; Miao-miao Zhao; Li Ma; Liang Yan (Journal of Zhejiang University-SCIENCE B, 2019)

Geochemical characteristics of dust aerosol availability in northwestern China - Xunming Wang; Jimin Sun; Mingrui Qiang; Caixia Zhang; Danfeng Li; Ting Hua; Hui Li; Lili Lang; Linlin Jiao; Diwen Cai; Wenyong Ma (Arabian Journal of Geosciences, 2019)

The Characteristics of Climate Change and Adaptability Assessment of Migratory Bird Habitats in Wolonghu Wetlands - Jun Ma; Baisha Weng; Wuxia Bi; Dengming Yan; Meng Li; Ting Xu; Lina Wang; Lin Wang (Wetlands, 2019)

ISRM Suggested Method: Determining Deformation and Failure Characteristics of Rocks Subjected to True Triaxial Compression - Xia-Ting Feng; Bezalel Haimson; Xiaochun Li; Chandong Chang; Xiaodong Ma; Xiwei Zhang; Mathew Ingraham; Kenichiro Suzuki (Rock Mechanics and Rock Engineering, 2019)

CO2 capture by ionic liquid membrane absorption for reduction of emissions of greenhouse gas - Jian-Gang Lu; Xiang Li; Yun-Xia Zhao; Hong-Lu Ma; Li-Fan Wang; Xin-Yi Wang; Yu-Fan Yu; Ting-Yu Shen; Hao Xu; Yu-Ting Zhang (Environmental Chemistry Letters, 2019)

Invasive Spartina alterniflora exhibits increased resistance but decreased tolerance to a generalist insect in China - Rui-Ting Ju; Ding Ma; Evan Siemann; Xiang Liu; Ji-Hua Wu; Bo Li (Journal of Pest Science, 2019)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Abnormal intrinsic cerebro-cerebellar functional connectivity in un-medicated patients with bipolar disorder and major depressive disorder - Yuan He; Ying Wang; Ting-Ting Chang; Yanbin Jia; Junjing Wang; Shuming Zhong; Huiyuan Huang; Yao Sun; Feng Deng; Xiaoyan Wu; Chen Niu; Li Huang; et al. (Psychopharmacology, 2018)

Absorption, translocation, and detoxification of Cd in two different castor bean (Ricinus communis L.) cultivars - Wenling Ye; Guifeng Guo; Fan Wu; Ting Fan; Hongjuan Lu; Haiyan Chen; Xuede Li; Youhua Ma (Environmental Science and Pollution Research, 2018)

The relative abundance of alkane‐degrading bacteria oscillated similarly to a sinusoidal curve in an artificial ecosystem model from oil‐well products - Guoqiang Li; Peike Gao; Bo Zhi; Bing Fu; Ge Gao; Zhaohui Chen; Mengli Gao; Mengmeng Wu; Ting Ma (Environmental Microbiology, 2018)
Summary Microbial phylogenetic diversity and species interactions in natural ecosystems have been investigated extensively, but our knowledge about their ecological roles, community dynamics and succession patterns is far from complete. This knowledge is essential to understand the complicated interactions of microorganisms in natural ecosystems. Here, an artificial ecosystem model of microorganisms was constructed from oil‐well products and cultivated in a chemostat to investigate the succession pattern of alkane‐degrading bacteria, a functional population in oil reservoirs. Their abundance was quantified by an improved qPCR technique. Our results showed that the phylogenetic structure of this artificial ecosystem model is stable during most of the chemostat cultivation process, while the genotype structure of alkane‐degrading bacteria containing alk B genes shifted and their relative abundance oscillated similarly to a sinusoidal curve, like the succession pattern of producers in the Lotka–Volterra model. These results suggest that some theoretical frameworks of macroecology may work well in microbial ecosystems and be an efficient tool to understand them.

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Surveillance of HIV-1 drug resistance in Xinjiang: high prevalence of K103N in treatment-naïve individuals - Zhanjun Shu; Yuying Chen; Aihemaiti Abudureyimu; Tingting Li; Ting Yuan; Jianping Ma; Xiaochun Li; Xiulan Ma; Chengyuan Jang; Gang Bao; Binlian Sun; Rongge Yang (Archives of Virology, 2018)

Bacterial community dynamics in the rhizosphere of a long-lived, leguminous shrub across a 40-year age sequence - Xiaofan Na; Xiaoran Li; Zeyong Zhang; Ming Li; Paul Kardol; Ting Ting Xu; Miao Wang; Xiaoning Cao; Fei Ma (Journal of Soils and Sediments, 2018)

Effects of aeolian processes on soil nutrient loss in the Gonghe Basin, Qinghai–Tibet Plateau: an experimental study - Xunming Wang; Lili Lang; Ting Hua; Hui Li; Caixia Zhang; Wenyong Ma (Journal of Soils and Sediments, 2018)

RETRACTED ARTICLE: SOC1 and AGL24 interact with AGL18-1, not the other family members AGL18-2 and AGL18-3 in Brassica juncea - Chao-chuang Li; Guan-peng Ma; Ting Xie; Jiao Chen; Zhi-min Wang; Ming Song; Qing-lin Tang (Acta Physiologiae Plantarum, 2018)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Variation in vegetation greenness along China’s land border - XunMing Wang; WenYong Ma; Ting Hua; DanFeng Li (Science China Earth Sciences, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Estimating cadmium concentration in the edible part of Capsicum annuum using hyperspectral models - Ting Wang; Hong Wei; Cui Zhou; Yanwen Gu; Rui Li; Hongchun Chen; Wenchao Ma (Environmental Monitoring and Assessment, 2017)

CCK-8 Inhibits Acute Morphine-induced Spatial Reference Memory Impairment in Mice - Shengchang Yang; Ting Feng; Dong Li; Di Wen; Chenteng Yang; Chunling Ma; Bin Cong (International Journal of Peptide Research and Therapeutics, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Enhancement of simultaneous algicidal and denitrification of immobilized Acinetobacter sp. J25 with magnetic Fe3O4 nanoparticles - Jun feng Su; Dong hui Liang; Ting lin Huang; Li Wei; Min Ma; Jinsuo Lu (Environmental Science and Pollution Research, 2017)

Inhalation of Roman chamomile essential oil attenuates depressive-like behaviors in Wistar Kyoto rats - Yingying Kong; Ting Wang; Rong Wang; Yichuan Ma; Shanshan Song; Juan Liu; Weiwei Hu; Shengtian Li (Science China Life Sciences, 2017)

A population association study of vitamin D receptor gene polymorphisms and haplotypes with the risk of systemic lupus erythematosus in a Chinese population - Xu-E Chen; Pu Chen; Shan-Shan Chen; Jin Lu; Ting Ma; Guang Shi; Ya Zhou; Ji Li; Liang Sheng (Immunologic Research, 2017)

Bacterial diversity in the rhizosphere of two phylogenetically closely related plant species across environmental gradients - Xiaofan Na; Ting Ting Xu; Ming Li; Fei Ma; Paul Kardol (Journal of Soils and Sediments, 2017)

Adsorption behavior of tetracycline by extracellular polymeric substrates extracted from Klebsiella sp. J1 - Ang Li; Shanshan Pi; Wei Wei; Ting Chen; Jixian Yang; Fang Ma (Environmental Science and Pollution Research, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Hydrogen peroxide is involved in abscisic acid-induced adventitious rooting in cucumber (Cucumis sativus L.) under drought stress - Xue-Ping Li; Qing-Qing Xu; Wei-Biao Liao; Zhan-Jun Ma; Xiao-Ting Xu; Meng Wang; Peng-Ju Ren; Li-Juan Niu; Xin Jin; Yong-Chao Zhu (Journal of Plant Biology, 2016)

A new pyrone derivative from an endophytic Aspergillus tubingensis of Lycium ruthenicum - Yang-min Ma; Ting Li; Cong-cong Ma (Natural Product Research, 2016)

Improved production of carotenoid-free welan gum in a genetic-engineered Alcaligenes sp. ATCC31555 - Wenwen Zhang; Zhaohui Chen; Mengmeng Wu; Zhong Shi; Feng Zhu; Guoqiang li; Ting Ma (Biotechnology Letters, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Construction of a high density linkage map and its application in the identification of QTLs for soluble sugar and organic acid components in apple - Baiquan Ma; Shuang Zhao; Benhong Wu; Dongmei Wang; Qian Peng; Albert Owiti; Ting Fang; Liao Liao; Collins Ogutu; Schuyler S. Korban; Shaohua Li; Yuepeng Han (Tree Genetics & Genomes, 2016)

A new furan derivative from an endophytic Aspergillus flavus of Cephalotaxus fortunei - Yang-Min Ma; Cong-Cong Ma; Ting Li; Jun Wang (Natural Product Research, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Impact of short-term climate variation and hydrology change on thermal structure and water quality of a canyon-shaped, stratified reservoir - Wei-Xing Ma; Ting-Lin Huang; Xuan Li; Hai-Han Zhang; Tuo Ju (Environmental Science and Pollution Research, 2015)

Inhibition of myosin light chain kinase reduces NADPH oxidase-mediated oxidative injury in rat brain following cerebral ischemia/reperfusion - Hong-Feng Zhang; Ting-Bo Li; Bin Liu; Zheng Lou; Jie-Jie Zhang; Jing-Jie Peng; Xiao-Jie Zhang; Qi-Lin Ma; Jun Peng; Xiu-Ju Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Subcutaneous Injections of the Mannose-Sensitive Hemagglutination Pilus Strain of Pseudomonas aeruginosa Stimulate Host Immunity, Reduce Bladder Cancer Size and Improve Tumor Survival in Mice - Tao Li; Li Yang; Sheng-jun Fu; Er-long Xiao; Xuan Yuan; Jian-zhong Lu; Bao-liang Ma; Ting-kai Shi; Zhi-ping Wang (Cell Biochemistry and Biophysics, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Inactivation of FoxM1 transcription factor contributes to curcumin-induced inhibition of survival, angiogenesis, and chemosensitivity in acute myeloid leukemia cells - Jing-ru Zhang; Fei Lu; Ting Lu; Wen-hao Dong; Peng Li; Na Liu; Dao-xin Ma; Chun-yan Ji (Journal of Molecular Medicine, 2014)

Identification and expression analysis of the E2F/DP genes under salt stress in Medicago truncatula - Tian-Yi Ma; Zi-Wei Li; Shu-Yong Zhang; Guo-Ting Liang; Jing Guo (Genes & Genomics, 2014)

The effects of different crossing-linking conditions of genipin on type I collagen scaffolds: an in vitro evaluation - Xiujie Zhang; Xueying Chen; Ting Yang; Naili Zhang; Li Dong; Shaoying Ma; Xiaoming Liu; Mo Zhou; Baoxing Li (Cell and Tissue Banking, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Porcine bone grafts defatted by lipase: efficacy of defatting and assessment of cytocompatibility - Naili Zhang; Mo Zhou; Yumin Zhang; Xusheng Wang; Shaoying Ma; Li Dong; Ting Yang; Lina Ma; Baoxing Li (Cell and Tissue Banking, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

An α-glucan isolated from root of Isatis Indigotica, its structure and adjuvant activity - Junjie Shan; Guohui Sun; Jinwei Ren; Ting Zhu; Peiyuan Jia; Wensheng Qu; Qian Li; Junhua Wu; Hao Ma; Song Wen; Yuxia Wang (Glycoconjugate Journal, 2014)

Alda-1 reduces cerebral ischemia/reperfusion injury in rat through clearance of reactive aldehydes - Si-Hai Fu; Hong-Feng Zhang; Zhong-Bao Yang; Ting-Bo Li; Bin Liu; Zheng Lou; Qi-Lin Ma; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Differential expression of VGLUT1 or VGLUT2 in the trigeminothalamic or trigeminocerebellar projection neurons in the rat - Shun-Nan Ge; Zhi-Hong Li; Jun Tang; Yunfei Ma; Hiroyuki Hioki; Ting Zhang; Ya-Cheng Lu; Fu-Xing Zhang; Noboru Mizuno; Takeshi Kaneko; Ying-Ying Liu; Mandy Siu Yu Lung; et al. (Brain Structure and Function, 2014)

Nutrients and oxygen alter reservoir biochemical characters and enhance oil recovery during biostimulation - Peike Gao; Guoqiang Li; Xuecheng Dai; Liubing Dai; Hongbo Wang; Lingxia Zhao; Yuehua Chen; Ting Ma (World Journal of Microbiology and Biotechnology, 2013)

Cloning, expression and characterization of a phosphoglucomutase/phosphomannomutase from sphingan-producing Sphingomonas sanxanigenens - Haidong Huang; Xiaoyan Li; Mengmeng Wu; Shengxiu Wang; Guoqiang Li; Ting Ma (Biotechnology Letters, 2013)

Walleye dermal sarcoma virus: expression of a full-length clone or the rv-cyclin (orf a) gene is cytopathic to the host and human tumor cells - Kun Xu; Ting Ting Zhang; Ling Wang; Cun Fang Zhang; Long Zhang; Li Xia Ma; Ying Xin; Chong Hua Ren; Zhi Qiang Zhang; Qiang Yan; Daniel Martineau; Zhi Ying Zhang (Molecular Biology Reports, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Characterization of microbial diversity and community in water flooding oil reservoirs in China - Lingxia Zhao; Ting Ma; Mengli Gao; Peike Gao; Meina Cao; Xudong Zhu; Guoqiang Li (World Journal of Microbiology and Biotechnology, 2012)

Pyrosequencing of a short fragment of the amelogenin gene for gender identification - Shujin Li; Ting Feng; Lihong Fu; Zhenhua Li; Chunguang Lou; Xiaojing Zhang; Chunling Ma; Bin Cong (Molecular Biology Reports, 2012)

A regional ocean reanalysis system for coastal waters of China and adjacent seas - Guijun Han; Wei Li; Xuefeng Zhang; Dong Li; Zhongjie He; Xidong Wang; Xinrong Wu; Ting Yu; Jirui Ma (Advances in Atmospheric Sciences, 2011)

Depressed Biofilm Production in Bacillus amyloliquefaciens C06 Causes γ-Polyglutamic Acid (γ-PGA) Overproduction - Jun Liu; Xin Ma; Yu Wang; Fang Liu; Junqing Qiao; Xiu-zhen Li; Xuewen Gao; Ting Zhou (Current Microbiology, 2011)

TEE monitoring for RA-horizontal paradoxical arterial air embolism during sitting-position surgery - Xin Ye; Ting Ma; TianLong Wang; MingFei Ge; CaiRong Wang; Jing Gao; XiaoHui Li (Science China Life Sciences, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Dynamics of soil properties and organic carbon pool in topsoil of zokor-made mounds at an alpine site of the Qinghai–Tibetan Plateau - Xiao Gang Li; Mei Lan Zhang; Zhuo Ting Li; Xiao Ming Shi; Qifu Ma; Rui Jun Long (Biology and Fertility of Soils, 2009)

Application of enzyme-linked immunosorbent assay for quantification of the insecticides imidacloprid and thiamethoxam in honey samples - Huixin Ma; Yanjun Xu; Qing X. Li; Ting Xu; Xintong Wang; Ji Li (Food Additives & Contaminants: Part A, 2009)

A novel endo-glucanase from the thermophilic bacterium Geobacillus sp. 70PC53 with high activity and stability over a broad range of temperatures - I-Son Ng; Chen-Wei Li; Yi-Fang Yeh; Po Ting Chen; Jiun-Ly Chir; Chin-Hua Ma; Su-May Yu; Tuan-hua David Ho; Chii-Gong Tong (Extremophiles, 2009)

Singlet oxygen formation and chlorophyll a triplet excited state deactivation in the cytochrome b 6 f complex from Bryopsis corticulans - Fei Ma; Xiao-Bo Chen; Min Sang; Peng Wang; Jian-Ping Zhang; Liang-Bi Li; Ting-Yun Kuang (Photosynthesis Research, 2009)

Improved biodesulfurization of hydrodesulfurized diesel oil using Rhodococcus erythropolis and Gordonia sp. - Guo-Qiang Li; Shan-Shan Li; Shi-Wei Qu; Qing-Kun Liu; Ting Ma; Lin Zhu; Feng-Lai Liang; Ru-Lin Liu (Biotechnology Letters, 2008)

PCR–DGGE method for analyzing the bacterial community in a high temperature petroleum reservoir - Jun Wang; Ting Ma; Lingxia Zhao; Jinghua Lv; Guoqiang Li; Fenglai Liang; Rulin Liu (World Journal of Microbiology and Biotechnology, 2008)

Improving ovary and embryo culture techniques for efficient resynthesis of Brassica napus from reciprocal crosses between yellow-seeded diploids B. rapa and B. oleracea - Jing wen; Jin-xing Tu; Zai-yun Li; Ting-dong Fu; Chao-zhi Ma; Jin-xiong Shen (Euphytica, 2008)

Repair of glutamate-induced excitotoxic neuronal damage mediated by intracerebroventricular transplantation of neural stem cells in adult mice - Juan Ma; Li-Jian Yu; Run-Di Ma; Yong-Ping Zhang; Juan-Zhi Fang; Xiao-Yu Zhang; Ting-Xi Yu (Neuroscience Bulletin, 2007)

Desulfurization of dibenzothiophene by Bacillus subtilis recombinants carrying dszABC and dszD genes - Ting Ma; Guoqiang Li; Jian Li; Fenglai Liang; Rulin Liu (Biotechnology Letters, 2006)

The application of very high resolution satellite image in urban vegetation cover investigation: A case study of Xiamen City - Cheng Chengqi; Li Bin; Ma Ting (Journal of Geographical Sciences, 2003)